GBIF Occurrence Download - Occdownload Gbif.Org (The Global Biodiversity Information Facility, 2015)
A dataset containing 542341919 species occurrences available in GBIF matching the query: All data. The dataset includes 542341919 records from 13200 constituent datasets: 11371 records from Mammal specimens. 979 records from Herbier_CNSF. 1 records from Nothrus segnis. 10 records from Ökowerk Emden. 13 records from Tiere im Teichgebiet. 482 records from Kühmark bei Wetzlar. 775 records from Insect (GNHM-IN). 106100 records from Fish (NSMK-PI). 43453 records from Plant (NSMK-PL). 1603 records from Fossil (MNHM-FO). 2568 records from Fish (NHMK-PI). 1 records from Oribates ovalis. 1 records from Oribates flammula. 1 records from Eremaeus hepaticus. 87 records from Biotop "Kohlbeke" (Berlin-Marzahn). 53985 records from BioMar - LIFE project. 197872 records from Field Museum of Natural History (Zoology) Invertebrate Collection. 16 records from Scorpaena bulacephala, a new species of scorpionfish (Scorpaeniformes: Scorpaenidae) from the northern Tasman Sea.. 375 records from Phthiraptera. 3 records from Revision der Ceratozetidae, 3. Ceratozetes laticuspidatus n. sp. (Arach., Acari, Oribatei). 3597 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209C sediments. 6 records from Hemichordata collection of National Museum of Nature and Science. 97 records from DMNH Eggs. 336 records from Especies de Anacroneuria (Insecta: Plecoptera: Perlidae) de Colombia, depositadas en el Museo de Entomología de la Universidad del Valle (Cali, Colombia). 865 records from (Appendix C) Benthic foraminifera extinction group species in DSDP Site 80-548. 104 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cathartidae. 9703 records from Hymenoptera de la Colección Entomológica del Instituto Alexander von Humboldt. 670 records from (Table 1) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Hole 133-815A. 3633 records from Bioimages. 1326 records from (Table T9) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zones P5-P7. 1 records from Arthropoden aus südostalpinen Höhlen.. 108936 records from Naturalis Biodiversity Center (NL) - Crustacea. 97 records from (Table 1) Distribution of calcareous nannofossils in ODP Hole 167-1017E sediments. 129 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 216 records from Registros biológicos del Humedal Santa Maria del Lago 1999-2013. 798 records from (Appendix Table 3) Relatice abundances of planktonic foraminiferal species in sediment core MD01-2390. 1003 records from Creación de un área protegida pública local en los municipios de Roldanillo, La Unión y Toro.. 46664 records from The Scottish Ornithologists' Club - Fife non-breeding bird 5km atlas 1991-99. 65 records from Revalidation and redescription of Pterocryptis anomala (Herre, 1933), a catfish (Teleostei: Siluridae) from southern China.. 775 records from A catalogue of the fishes held in the Istanbul University, Science Faculty, Hydrobiology Museum.. 5549 records from Diplopoda (NSMK-DI). 398 records from Tsetse flies of East Africa update. 993 records from Rossendale Ornithologists' Club - ROC RSPB Farmland Species Survey Dataset. 58475 records from Oregon State University Herpetological Collection. 227 records from Colección de Salamandras Museo de La Salle Bogotá (MLS). 27988 records from Argyll Bird Club - Bird records for Argyll for the years 2002 and 2003. 3367 records from (Figure 4) Distribution of dinoflagellate cysts in the Albian/Cenomanian of DSDP Hole 79-547A. 139 records from The Bat Conservation Trust - Woodland Survey. 396 records from Chironomid Specimen records in the Chironomid DNA Barcode Database. 151010 records from Marie-Victorin Herbarium (MT). 161085 records from Molluscs collection (IM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 8748 records from British Lichen Society - BLS Rare and Threatened Lichen Records: Wales. 373 records from Otter survey of Ireland 2004 & 2005. 3107 records from The Vascular Plants Collection of the Regensburgische Botanische Gesellschaft. 10512 records from (Table T2) Plankontic foraminifera stratigraphy of ODP Hole 184-1146A. 18 records from Rita macracanthus, a new riverine catfish (Teleostei: Bagridae) from South Asia.. 140 records from Three new percid fishes (Percidae: Percina) from the Mobile Basin drainage of Alabama, Georgia, and Tennessee.. 475 records from Equinodermos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CRBMeq-UV). 1252 records from Aquatic Coleoptera Conservation Trust - SNH site condition monitoring of SSSIs for water beetles 2010. 201 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-7. 2 records from Oribatids from Switzerland I. (Acari: Oribatida). (Acarologica Genavensia LXXXI). 11789 records from JOI - Herbário Joinvillea. 2312 records from Mycological collection of the National Museum. 30 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto1-10. 71 records from Occurrence data of Ectyphus and Parectyphus (Diptera: Asiloidea: Mydidae). 16 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rostratulidae. 6543 records from University of Ghent - Zoology Museum - Vertebratacollectie. 2356 records from Naturalis National Natural History Museum (NL) – Aves_Types. 7 records from Peckoltia sabaji, a new species from the Guyana Shield (Siluriformes: Loricariidae).. 5 records from Arthropoden aus südostalpinen Höhlen.. 311768 records from Naturalis Biodiversity Center (NL) - Hymenoptera. 108 records from (Table 3) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-844B. 338 records from (Tab. 9.C) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 6848 records from Ratti Master Thesis / Fraser Valley, British Columbia. 2661 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del Parque Nacional Natural Tayrona. 2 records from Benthic hard-bottom communities abundance at X-Huinay in 2010. 468533 records from Royal Dutch Angling Association (SVN) - Piscaria. 73514 records from National Trust - Wicken Fen nature reserve species data held by The National Trust. 535913 records from BioFokus. 155 records from (Appendix 1) Coral analysis and isostatic rebound effects from different Holes of IODP Expedition 310. 2 records from The first record of a fly of the family Milichiidae (Diptera) interacting with an ant of the genus Polyrhachis Smith, 1857 (Hymenoptera: Formicidae). 396 records from RSPB - 2008 Farmland Bird Survey North East Wales - RSPB/CCW. 45 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Spheniscidae. 1957 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD unverified freshwater fish data up to current day. 83 records from Eden Rivers Trust - White-clawed crayfish (Austropotamobius pallipes) distributions within four sub-catchments of the River Eden Catchment, Cumbria 2007-2008. 31 records from Siphonaptera. 2 records from Enchelycore nycturanus, a new moray eel from South Africa (Teleostei: Anguilliformes: Muraenidae).. 5953 records from SPFw - Xiloteca do Instituto de Biociências da Universidade de São Paulo. 132 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0011B. 10072 records from Guadeloupe_Herbier. 28385 records from Plan de vertebrados de la Patagonia. 385 records from (Appendix E) Size measurements of Selenopemphix undulata sp. nov. in ODP Site 202-1233. 57 records from The Game & Wildlife Conservation Trust - Capercaillie sightings Speyside 2011. 24 records from A revision of the Indo-Pacific fish genus Caragobius (Gobiidae: Amblyopinae).. 1 records from Nothrus spinifer. 2707 records from Colección de Coleoptera (Scarabaeoidea) del sureste de la Península Ibérica de la Universidad de Granada. 1904 records from Terrestrial Heteroptera Recording Scheme (Shieldbugs & allied species) - Flickr (01) Shieldbugs & allied species. 100 records from Royal Horticultural Society - Nezara viridula records held by the Royal Horticultural Society. 1311 records from (Table 3A) Occurrence and estimated abundance of planktonic foraminifers at DSDP Holes 85-572 and 85-572A. 457 records from Royal Horticultural Society - European Pear Rust (Gymnosporangium sabinae) monitoring. 277 records from (Table 1) Abundances of planktonic and benthic foraminifera in ODP Hole 130-806B. 99300 records from Landesmuseum Kärnten. 10030 records from Free-living marine Nematodes from San Julián bay (Santa Cruz, Argentine), 2009.. 4 records from Taxonomy of Afrotropical and West Palaearctic ants of the ponerine genus Hypoponera Santschi (Hymenoptera: Formicidae).. 164 records from EcoRecord - Reptile records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 51110 records from Inventaire National du Patrimoine Naturel : Insectes Orthoptères de France. 15 records from Taxonomy of European Damaeidae (Acari: Oribatida) I. Kunstidamaeus Miko, 2006, with comments on Damaeus sensu lato. 160 records from Scottish Natural Heritage - Distribution of Scottish wildcats (Felis silvestris) in Scotland (2006-2008) â database extract (breeding and non-breeding records). 118 records from A Tenebrionid beetle’s dataset (Coleoptera, Tenebrionidae) from Peninsula Valdés (Chubut, Argentina). 6060 records from Free-living Nematodes from Patagonia coastal lagoons (Chubut, Santa Cruz, Argentina).. 27 records from Redescription of Apteronotus mariae (Eigenmann & Fisher, 1914) and the taxonomic status of Apteronotus jurubidae (Fowler, 1944) (Gymnotiformes: Apteronotidae).. 3509 records from Entocytheridae (Ostracoda) World Database. 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 4438 records from ISE - Herbário ISE. 457 records from Microbial Observatory of the Laboratoire Arago. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 2925 records from Herbarium specimens of the Muséum d'Histoire Naturelle d'Autun (AUT). 401 records from (Fig. 7) Coccolith species abundance of sediment core GeoB11035-1. 2 records from (Table 10) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-854B. 8220342 records from OEH Atlas of NSW Wildlife. 273 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 322-C0012A. 36 records from Two new species of Isbrueckerichthys Derijst, 1996 (Siluriformes: Loricariidae) from the rio Paranapanema basin, Brazil.. 1352 records from (Figure 9) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-536. 9543 records from RSPB - Wader survey on Uist in 2007 (RSPB/BTO). 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 330041 records from University of British Columbia Herbarium (UBC) - Vascular Plant Collection. 10 records from (Table C) Fauna associated with Bathymodiolus azoricus mussel beds within the Rainbow hydrothermal field, Mid-Atlantic Ridge. 1741 records from EcoRecord - Mollusc records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 238 records from Seven new species of Spathidexia Townsend (Diptera: Tachinidae) reared from caterpillars in Area de Conservación Guanacaste, Costa Rica. 10 records from A new wobbegong shark, Orectolobus hutchinsi n. sp. (Orectolobiformes: Orectolobidae) from southwestern Australia.. 52381 records from UAM Herbarium (ALA), Cryptogam Collection (Arctos). 172345 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine) data for Great Britain and Ireland. 5796 records from Real Jardin Botanico: Dibujos de la Real Expedición Botánica del Nuevo Reino de Granada (1783-1816), dirigida por J.C. Mutis. 130 records from (Table S1) Pb/U zircon ages of ODP Hole 118-735B. 8934780 records from Botanical Society of the British Isles - Vascular Plants Database. 1238 records from Insect Collection (CeStuBio). 1 records from Celaeno plicata. 83 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Polioptilidae. 28 records from Two new species of Pamphobeteus Pocock 1901 (Araneae: Mygalomorphae: Theraphosidae) from Brazil, with a new type of stridulatory organ. 7478 records from Merseyside BioBank - North Merseyside Reptiles and Amphibians (unverified). 231 records from (Appendix A) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 107-654A. 129 records from (Table 2) Planktonic foraminifer abundance in ODP Section 167-1021C-10H-2. 191 records from Herpetofauna laguna El Tinije. 58 records from (Table 4a) Range chart of benthic and planktonic foraminifera of ODP Hole 127-796A. 20 records from Heteroptera - SMNG. 41 records from Two new species of Pseudoscopelus (Teleostei: Chiasmodontidae), with a new diagnosis for the genus.. 20043 records from Mollusca collection of National Museum of Nature and Science. 250 records from Taxonomic revision of the seasonal South American killifish genus Simpsonichthys (Teleostei: Cyprinodontiformes: Aplocheiloidei: Rivulidae).. 244 records from Scottish Natural Heritage - The ecology of Najas flexilis (Slender naiad). 74 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria ( Gastropoda ). 10633 records from Biological Records Centre - Collembola Recording Scheme. 47601 records from CRCM Vertebrate Collection. 31936 records from Records of Avifauna of Wetlands around Keoladeo National Park, Bharatpur, India. 20870 records from HUEM - Herbário da Universidade Estadual de Maringá. 74 records from (Table 3) Abundance of benthic foraminifera and ostracoda in bottom sediments from the Ashadze-1 Hydrothermal Field. 66081 records from HUFU - Herbarium Uberlandense. 661414 records from Phanerogamic Botanical Collections (S). 2922 records from National Lesser Horseshoe Bat Database. 3 records from MSB Mammal Observations (Arctos). 1152 records from (Table 12) Benthic foraminifera in Eocene-Oligocene sediments of DSDP Hole 90-592. 7735 records from CSUC Vertebrate Collection. 1 records from Hoplophora globosa. 90189 records from African Rodentia. 279 records from Dieta del Piquero Café (Sula leucogaster etesiaca) en el Parque Nacional Natural Gorgona, Pacífico colombiano.. 1 records from Un chilopode cavernicole nouveau de Yougloslavie Bothropolys magnificus n. sp.. 62283 records from PRECIS (KwaZulu-Natal Herbarium). 712 records from Herbier G. Garapin (BOUM). 5824 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Yser. 1 records from (Table 4) Thecosomata in ODP Hole 134-831A. 477 records from Visfauna - Juvenile and adult fishes in riparian habitats along the river Leie. 1334 records from (Table 5) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-848B. 66 records from (Table T8) Calcareous nannofossil stratigraphy of ODP Hole 198-1211A. 33 records from Revision von Suctobelba trigona (Michael, 1888). 3 records from Trichomycterus giganteus (Siluriformes: Loricarioidea: Trichomycteridae): a new catfish from the Rio Guandu basin, southeastern Brazil.. 1 records from Nothrus runcinatus. 19 records from Inventario de Aves Pauto J, Yopal, Casanare. 113 records from Studies on species of Holarctic Pardosa groups (Araneae, Lycosidae). VII. The Pardosa tesquorum group. 37 records from Museu Paraense Emilio Goeldi - Schizomida Collection. 106428 records from Jordal. 267464 records from MVZ Herp Collection (Arctos). 1988 records from (Appendix 2) Benthic foraminifera in ODP Hole 160-963A. 28702 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mammalia. 5729 records from Alterra (NL) - Entomofauna inventory in cattle grazed dune grassland. 1702 records from BioGIS - Bryophytes - HUJ collections. 65 records from A new species of Rineloricaria (Siluriformes: Loricariidae) from the Paraná and Uruguay River basins, Misiones, Argentina.. 5709 records from Coleoptera of Piska Forest. 4108 records from Anthomyiidae Study Group - Anthomyiidae records for Great Britain. 6992 records from RSPB - Stone-curlew Annual Surveys (RSPB/Natural England). 1998 records from Aves de la cuenca media del río Bogotá. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 51 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 4198 records from Planktic foraminifera (%) of sediment core MD96-2085. 22 records from Anostomoides passionis, a new fish species from rio Xingu, Brasil (Characiformes: Anostomidae).. 1353 records from Colección de Entomología - Diptera - Ceratopogonidae. 1 records from Damaeus concolor. 1 records from Pollen analysis of sediment profile KAIX_B from Kaiserwinkel. 3 records from Revision of the ant genus Perissomyrmex with notes on the phylogeny of the tribe Myrmecinini.. 59016 records from Biological Records Centre - Isopoda (Interim dataset). 8 records from A review of the ant genus Metapone Forel from Madagascar.. 35 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2001. 9302 records from Ants from the Paraguayan dry Chaco. 55 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cardinalidae. 1300 records from Composición florística y estructura de una parcela permanente en bosques húmedos tropicales del río Cajambre (Guandal), municipio de Buenaventura, Valle del Cauca. 27975 records from The Environmental Sample Collection of the Arthropoda Varia Section at the Zoologische Staatssammlung München. 38543 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD other mammal data up to current day. 2418 records from (Figure 9) Distribution of Maaestrichtian planktonic foraminifera in ODP Hole 132-810C. 68221 records from University of Vienna, Institute for Botany - Herbarium WU. 379 records from WNMU Fish Collection (Arctos). 2147 records from University of Amsterdam (NL) - Páramo Vegetation Research, National Natural Park El Cocuy, Colombia. 44051 records from Alterra (NL) - Entomofauna inventory in peat swamps. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty and Biswas. 4 records from First record of Limnatis paluda (Hirudinida, Arhynchobdellida, Praobdellidae) from Kazakhstan, with comments on genetic diversity of Limnatis leeches. 15387 records from UFG - Herbário da Universidade Federal de Goiás. 4 records from New data on recently described rodent species Paulina's Limestone Rat Saxatilomys paulinae Musser, Smith, Robinson & Lunde, 2005 (Mammalia: Rodentia). 6 records from Review of the genus Metopheltes Uchida, 1932 (Hymenoptera, Ichneumonidae) with description of a new species from Vietnam. 1808 records from University of Amsterdam (NL) - Páramo vegetation research, Ecuador.. 1025 records from (Appendix 2) Absolute abundance of nannofossils in ODP Hole 183-1135A. 1592 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Furnariidae. 5181 records from MFS - Herbário Profª. Drª. Marlene Freitas da Silva. 154 records from (Table T1) Calcareous nannofossil stratigraphy in ODP Hole 186-1150A sediments. 326 records from Colección nacional de palmas de Colombia - JBQ. 1710 records from (Table 8E) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 89-586B, Sections 19-4 through 25-5. 304 records from Succession of benthic hard-bottom communities abundance at station Errina2012_IS_solar2. 202 records from Biodiversity Information Service for Powys and Brecon Beacons National Park - Distribution of Impatiens glandulifera Royle along the river Irfon during June 2010. 3592 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Invasive Insecta. 159 records from University of Amsterdam (NL) - Páramo vegetation research, Venezuela.. 78 records from Guyane_française_caféier. 10 records from Merodoras nheco, new genus and species from Rio Paraguay basin, Brazil (Siluriformes, Doradidae), and nomination of the new subfamily Astrodoradinae.. 2494 records from Colección de peces dulceacuícolas de Costa Rica. 3087 records from Herpetile collection, Natural History Museum, University of Oslo. 2546 records from The atlas of butterflies in Kraków. 231131 records from MVZ Mammal Collection (Arctos). 165 records from Palaeoclimate records over the past 22,000 years of sediment core GeoB10053-7. 610 records from RSPB - Farmland bird database in Dumfries and Galloway, 1999-2010 (RSPB). 10 records from Inventarios de Murciélagos Pauto M, La Primavera, Yopal, Casanare. 8136 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Coelenterata. 3204 records from Faunal Inventory of Morysin Nature Reserve. 42 records from (Table 2) Benthic foraminifers at DSDP Hole 72-515A. 4251 records from Aves de la cuenca media del río Chambery, Caldas. 288 records from Fungi of Słowiński National Park, Poland. 15181 records from British Lichen Society - BLS Lichen Database: Welsh churchyards. 1654 records from RAVON (NL) - Fish observations extracted from Redeke (1907). 408 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Columbidae. 248 records from Millipedes and centipedes in German greenhouses (Myriapoda: Diplopoda, Chilopoda). 420 records from Reptilia Collection of Museum and Institute of Zoology PAS. 6179 records from Southern Cape herbarium. 9788 records from SANT-Lich. 1616 records from Gloucestershire Centre for Environmental Records - Gloucestershire Reptiles. 1205 records from Ecology, structure and dynamics of private plantations of Teak (Tectona grandis Lf) of the Department of the Atlantic (South Benin), 2011. 5248 records from (Figure 2) Range and distribution chart of dinoflagellate cysts recovered from Campanian to Maestrichtian sediments at DSDP Hole 95-612. 35 records from Neoniphon pencei, a new species of holocentrid (Teleostei: Beryciformes) from Rarotonga, Cook Islands. 38689 records from Marine species distributions in Irish coastal waters. 3175 records from Centre for Genetic Resources, the Netherlands, Indigenous Trees and Shrubs. 6239 records from (Figure 1) Distribution of dinoflagellate cysts in the mid-Cretaceous of DSDP Hole 79-545. 1 records from Zetes longiusculus. 64 records from Reuniting males and females: redescriptions of Nuisiana arboris (Marples 1959) and Cambridgea reinga Forster & Wilton 1973 (Araneae: Desidae, Stiphidiidae). 980 records from (Table AT7) Planktonic foraminiferal stratigraphy of ODP Hole 182-1132B. 10358 records from Census of the flora of Benin. 1 records from Newly discovered sister lineage sheds light on early ant evolution. 1020718 records from Consortium of California Herbaria. 13597 records from Orthopteroidea. 30872 records from Online Atlas of vascular plants 2012-2020. 2805 records from Fundación Miguel Lillo - Colección Mamíferos. 15637 records from CCBER Herpetology Collection. 3091629 records from Naturalis Biodiversity Center (NL) - Botany Leiden. 4686 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Types. 70222 records from Dorset Environmental Records Centre - Dorset SSSI Species Records 1952 - 2004 (Natural England). 128959 records from Australian National Wildlife Collection provider for OZCAM. 89874 records from ecoscope_observation_database. 2376 records from DVPR - Herbário da Universidade Tecnológica Federal do Paraná - Dois Vizinhos. 215 records from (Table 8) Benthic foraminifera genera assemblage at DSDP Section 80-548A-28. 167 records from Faunistic diversity of spiders (Araneae) in Galichitsa mountain (FYR Macedonia). 142691 records from Vascular Plants, Field notes, Agder naturmuseum (KMN). 12065 records from Tromsø Museum, Bryophytes. 356 records from Morphologische Daten von Puffinus creatopus. 941 records from (Appendix 1) Benthic foraminifera in eastern equatorial Indian Ocean surface sediments. 25 records from Glyptothorax botius (Hamilton, 1822), a valid species of catfish (Teleostei: Sisoridae) from northeast India, with notes on the identity of G. telchitta (Hamilton, 1822).. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 35 records from Osteology and phylogeny of Parioglossus (Teleostei, Gobioidei), with a revised key to the species.. 1025 records from Irish Marine Turtle Database. 18 records from A new species of Anabarhynchus (Diptera: Therevidae) from an ocean beach in south east Victoria. 34 records from New records in vascular plants alien to Kyrgyzstan. 575 records from Aspilota-group (Hymenoptera: Braconidae: Alysiinae) diversity in Mediterranean Natural Parks of Spain. 8410 records from Aves Acuáticas de las sabanas inundables del Meta y Casanare. 859 records from Extra-andean Patagonian Herbarrium -CONICET- Argentina. 204 records from (Table 8) Sample mass, sand fraction and relative abundances of planktonic foraminifera in ODP Holes 127-794A and 127-197B. 232 records from (Table A1) Stratigraphic distribution of calcareous nannofossils of ODP Hole 198-1210A. 51527 records from IAC - Herbário do Instituto Agronômico de Campinas. 74 records from (Table T5) Cretaceous calcareous nannofossil abundance of ODP Hole 173-1069A. 7427 records from Weevils of the Tatra Mts.. 20 records from Marine gastropods and other remains profile from sediment core AV14_K2-3. 561820 records from Bee Biology and Systematics Laboratory. 1 records from Egg capsules of Atlantoraja cyclophora (Regan, 1903) and A. platana (Günther, 1880) (Pisces, Elasmobranchii, Rajidae).. 78 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: géneros Saltator & Saltatricula. 511 records from Coleoptera of Swierklaniec Forest. 60672 records from QLD DERM Coastal Bird Atlas (Trial). 163 records from (Table 4) Benthic foraminifera genera assemblage at DSDP Section 80-548A-11-3. 2480 records from Woodland Condition Survey Group - Plants recorded during the non-SSSI woodland condition survey 2011. 4734 records from Marine Biological Association - Volunteer sightings data held by the DASSH Data Archive Centre. 88901 records from Naturalis National Natural History Museum (NL) – Insecta_Lepidoptera_SE Asia and other regions. 1172 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1215A sediments. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 52797 records from FLOR - Herbário do Departamento de Botânica da Universidade Federal de Santa Catarina. 528 records from Revision of the Malagasy genus Trichoteleia Kieffer (Hymenoptera, Platygastroidea, Platygastridae) - Darwin Core Archives. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Aramidae. 60573 records from Ornithology Collection Non Passeriformes - Royal Ontario Museum. 2 records from Scottish Natural Heritage - Survey of White-clawed crayfish Austropotamobius pallipes in Scotland. 834 records from Diptera Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 51390 records from Scottish Wildlife Trust - The Scottish Squirrel Database. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 23052 records from RSPB - Swift Inventory of Low-Level Screaming Parties in the UK, 2009 (RSPB and Swift Conservation Groups). 422 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Hirundinidae. 167 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Psittacidae. 8 records from Order Diptera, family Mydidae. 119 records from Redescription of Tetramorium forte Forel, 1904 (Insecta: Hymenoptera: Formicidae), a western Mediterranean ant species.. 3082 records from dec2011. 1 records from Hoplophora laevigata. 1603 records from Cambridgeshire & Peterborough Environmental Records Centre - CPERC Recorders day at Waterbeach barracks and airfield. 9 records from Polyrhachis (Myrma) cyaniventris F. Smith, 1858 (Hymenoptera: Formicidae) and a related new ant species from the Philippines.. 1284 records from Collection of Heteroptera. 16 records from Tettigettalna josei (Boulard, 1982) (Hemiptera: Cicadoidea): first record in Spain, with notes on the distribution, genetic variation and behaviour of the species. 42659 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Aves. 25 records from (Table 1) Osmium isotope ratios and Re-Os element content in bulk sediments of ODP Hole 121-758A. 1336963 records from AntWeb. 1 records from Red list project inventory, bryophytes. 485 records from National Taiwan Ocean University. 1 records from Oribates fuscipes. 6 records from (Table 1) Abundance of ciliates, dinoflagellates, nauplii and krill at different stations in the Godthabsfjord. 1 records from Oribates calcaratus. 8332 records from Joint Nature Conservation Committee - Scotland Otter Survey Database. 2 records from Pollen analysis of sediment profile AUL00 from Steeger See. 568 records from Coleccion Paleoinvertebrados CCT Mendoza - CONICET. 4354 records from Portuguese Seaweeds. 10102 records from Herbarium Vonderau - FULD. 5581 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-994C. 476 records from Caracterización Aves IAI-GAICA: Proyecto Cambio Climático. 3 records from A Partial Revision of the Genus Metabelba Grandjean (Oribatei, Acarina). 768 records from (Table 3) Benthic foraminifera in Southwest Indian Ocean surface sediments. 296072 records from Dr Francis Rose Field Notebook Project - Field Notebook Records of Dr Francis Rose 1950's to 1990's. 5 records from A new species and records of Diolenius Thorell, 1870 (Araneae: Salticidae) from New Guinea. 4 records from Fossil (SMNH-FO). 2007 records from Palaeobiology collection, FAU Erlangen. 9 records from The Oribatid Family Phthiracaridae II. Redescription of Phthiracarus laevigatus (C. L. KOCH). 13583 records from Highland Biological Recording Group - HBRG Fungus, Lichen and Lower Plants Dataset. 2 records from A new phreatic catfish of the genus Phreatobius Goeldi 1905 from groundwaters of the Itenez River, Bolivia (Siluriformes: Heptapteridae).. 41 records from (Table T5) Calcareous nannofossil abundance of ODP Hole 189-1172A sediments. 1 records from A new species of Cottunculus (Teleostei: Psychrolutidae) from the Mid Atlantic Ridge.. 35287 records from Bryophyta collection of the Botanical Museum of the University of Oulu. 2 records from Postia alni Niemelä & Vampola (Basidiomycota, Polyporales) – member of the problematic Postia caesia complex – has been found for the first time in Hungary. 4579 records from Herbarium WRSL, Flora of the Silesia. 145 records from (Tab. 9.B) Presence and abundance of benthic fauna at station FINO 1 in 2005-2007. 304 records from John Muir Trust - Bryophytes of Glen Nevis Woods 1987-1988. 4 records from Austromorium, a new myrmicine ant genus from Australia (Hymenoptera: Formicidae).. 19 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC03. 5733 records from Small Mammal Research Database. 352 records from Scottish Natural Heritage - Recovery of the medicinal leech Hirudo medicinalis in Scotland - Phase II. 26 records from Description of a new cyprinid species, Labeo meroensis n. sp. (Teleostei: Cyprinidae), from the River Nile.. 177466 records from CAS Entomology (ENT). 2116 records from Collection entomologique Pierre Lachiver. 51 records from Six new species of ants (Insecta: Hymenoptera: Formicidae) from Egypt.. 59534 records from Zoology (Museum of Evolution - Uppsala). 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 1 records from Zetes cespitum. 8007 records from Segunda caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 548 records from (Tab. 9.D) Presence and abundance of benthic fauna at station FINO 1 in 2005. 46954 records from SPSF - Herbário Dom Bento José Pickel. 28 records from (Table 2) Oligocene to Pliocene nannofossil range chart for ODP Hole 134-828A. 2509 records from Type Specimen Database of Museum and Institute of Zoology PAS. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 36432 records from RSPB - Corncrake national surveys - raw data (SCARABBS). 182 records from (Table VII) Benthic foraminifera abundance in the Great Belt Channel. 336 records from (Table T3) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones P5-P6b. 2 records from Papakula and Hesydrimorpha: how two spider genera were described from the same species collected from the same locality (Araneae: Pisauridae). 2 records from Rivulus uatuman sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new miniature killifish from the central Brazilian Amazon.. 71 records from (Table 5) Selection of Holocene-Pleistocene boundaries in ODP Leg 139 holes. 1 records from Descriptions de nouvelles fourmis éthiopiennes (quatrième note).. 239 records from Systematic review of the neotropical shovelnose catfish genus Sorubim Cuvier (Siluriformes: Pimelodidae).. 1387717 records from Fishbase. 6 records from Histoire naturelle des Hymenopteres. Deuxieme partie: Les Formicides.. 6541 records from Likona Invertebrates. 64 records from (Table 2) Planktonic foraminifera species found in sediment trap samples and bottom sediments at Station Vy20-3178. 1 records from Review of the ant genus Nesomyrmex (Hymenoptera: Formicidae: Myrmicinae) in southern Africa.. 3797 records from HUCO - Herbário da Universidade Estadual do Centro-Oeste. 233 records from Dataset for Review of Mimosticus Sharp (Coleoptera: Staphylinidae). 1206 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1172A sediments. 270 records from HTSA-Carpoteca - Carpoteca do Trópico Semiárido. 35 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rhinocryptidae. 116 records from Concentration of organic-walled dinoflagellate cysts from 116 marine surface samples. 2258 records from Biological Records Centre - Muscidae (Diptera) records from Britain and Ireland to 1985. 62 records from The North American spider genera Paratheridula, Tekellina, Pholcomma and Archerius (Araneae: Theridiidae). 2421 records from BOTUw - Xiloteca "Profa. Dra. Maria Aparecida Mourão Brasil". 1196 records from Entomological collection of the National Museum. 122 records from A taxonomic revision of the catshark genus Haploblepharus Garman 1913 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 26880 records from KUBI Ornithology Tissue Collection. 7 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 1 records from Hoplophora ferruginea. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 28626 records from SANT-Algae. 1124142 records from PRECIS. 234 records from (Table T4) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1211B, Shatsky Rise, Pacific Ocean. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 2494 records from Marine Environmental Monitoring - Marine Turtles. 49 records from (Table 8) Pliocene to Pleistocene nannofossil range chart for ODP Hole 134-833B. 1 records from Celaeno obsoleta. 28383 records from Notes from the Mycology Herbarium, Oslo (O). 59799 records from Plant Specimen from Herbarium (HIB) in China, Wuhan Botanical Garden, Chinese Academy of Sciences. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 662 records from Alterra (NL) - Microarthropods inventory in grassland and arable land. 1 records from Oribates gilvipes. 389 records from Amphibian and Reptilian (KIEE-AR). 5730 records from Cercle des mycologues de Montréal Fungarium (CMMF). 225 records from (Table T2) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 6237 records from Plecoptera. 10137 records from Royal Horticultural Society - RHS lily beetle (Lilioceris lilii) monitoring. 121542 records from SP - Herbário do Estado "Maria Eneyda P. Kaufmann Fidalgo" - Coleção de Fanerógamas. 55 records from (Table S2a) Nannofossil species richness in the Bass River section. 4738 records from (Table 3) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-845A. 8585 records from RSPB - Bird Conservation Targeting Project (BCTP) in the UK, archived data (2001-2008) - sensitive records. 13094 records from Mammalia Collection of Institute of Systematics and Evolution of Animals. 2 records from Simpsonichthys radiosus sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual killifish from the upper Rio Tocantins basin, central Brazil.. 4689 records from Funed-Pol - Coleção de lâminas de grãos de pólen. 22 records from Colección Parasitológica del Centro Nacional Patagónico (CNP-PAR). 13909 records from Albany Museum. 3 records from Fossil occurrence of calcareous nannofossils from IODP Hole 319-C0009A. 2498 records from (Table T1) Abundance of dinoflagellates and other palynomorphs in ODP Hole 189-1168A sediments. 1866 records from Colección de Crustacea del Museo Nacional de Historia Natural de Chile. 1 records from A new species of the genus Sinanapis (Araneae: Anapidae) from Lam Dong province, southern Vietnam.. 190 records from Inventaire National du Patrimoine Naturel : Observations d'hippocampes et syngnathes de France métropolitaine: Programme Hippo-ATLAS. 25530 records from (Table 1) Distribution of planktonic foraminifera in ODP Site 130-806. 33070 records from CSIRO Ichthyology provider for OZCAM. 9216 records from Inventaire National du Patrimoine Naturel : Crustacés Décapodes de France. 24 records from (Table 1) Stage of the lemming cycle and nesting parameters of the greater snow geese between 1996-2005, Bylot Island. 29587 records from EPA River Biologists data. 2338 records from Glasgow Museums BRC - Mammal records for Clyde Faunal Area, 1850 to 2007. 9 records from (Appendix B) Relative abundance of benthic foraminifera morphotypes in ODP Hole 138-844C. 216 records from (Table A2) Stratigraphic distribution of major planktic foraminifer species of ODP Hole 198-1210A. 190 records from Relative abundance of ostracods in sediment core Sv09. 7693 records from NHM, Heteroptera. 292 records from Gymnotus ucamara: a new species of Neotropical electric fish from the Peruvian Amazon (Ostariophysi: Gymnotidae), with notes on ecology and electric organ discharges.. 4544 records from Orthoptera collection (EO) of the Muséum national d'Histoire naturelle (MNHN - Paris). 163199 records from Plant Specimen in Yunnan, China from Herbarium (PE),Institute of Botany, Chinese Academy of Sciences. 461 records from Guadeloupe_Bananier. 5771 records from Segunda caracterización biológica de plantas del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 27639 records from Cicadelidos (Hemiptera: Cicadellidae) de Colección Entomológica del Instituto Alexander von Humboldt. 2731 records from Collection du Musée d'Histoire Naturelle de Nice. 246 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2005-2006. Part 3. 2513 records from Carabidae of the Tatra Mts.. 116 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Troglodytidae. 75791 records from SAIAB. 559 records from (Table 2) Planktonic foraminifera community at DSDP Hole 94-610. 829 records from Devon Biodiversity Records Centre - Dartmoor National Park survey data (1910-1970). 16 records from Taxonomic review of the genus Wasmannia.. 146382 records from Swedish Board of Fisheries (Fiskeriverket) - Institute of Coastal Research. 66 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Haematopodidae. 3 records from Redescription of Platynaspis flavoguttata (Gorham) (Coleoptera, Coccinellidae) and notes on nomenclature of Platynaspis kapuri Chakraborty & Biswas. 18896 records from SPF - Herbário da Universidade de São Paulo. 262155 records from South East Wales Biodiversity Records Centre - CCW Regional Data : South East Wales Non-sensitive Species Records. 32 records from (Table T1) Dinoflagellate cyst and spore/pollen yield and preservation in ODP Leg 188 sites. 8 records from A new species of the genus Nothobranchius (Cyprinodontiformes: Nothobranchiidae) from the coastal area of northeastern Mozambique.. 66722 records from SANT herbarium vascular plants collection. 4461 records from Paläontologie Marburg. 26 records from A new species of the Asian schilbid catfish genus Clupisoma from Myanmar, with a redescription of Clupisoma prateri Hora (Osteichthyes: Siluriformes: Schilbidae).. 965 records from Thames Valley Environmental Records Centre - Nature Conservancy Council Oxfordshire Fen Survey 1983 (as held by Thames Valley Environmental Records Centre). 17618 records from BioGIS - Mammals - INPA database. 5 records from (Figure 8) Relative abundance of nannoliths at DSDP Hole 62-464. 6 records from Collection Myriapoda - SNSD. 1 records from Miriapodi di alcune grotte della Campania. 165769 records from KUBI Mammalogy Collection. 8 records from Pomacentrus aurifrons, a new species of damselfish (Pomacentridae) from Melanesia.. 1 records from new species of the fungus-farming ant genus Mycetagroicus Brandao & Mayhe-Nunes A new species of the fungus-farming ant genus Mycetagroicus Brandao Mayhe-Nunes (Hymenoptera, Formicidae, Attini).. 10 records from A new Neoplatyura Malloch from Finland (Diptera, Keroplatidae). 9 records from Kryptopterus platypogon, a new silurid catfish (Teleostei: Siluridae) from Borneo.. 185 records from Macrozoobenthos abundance of the intertidal zone of a sandy beach at the Island Algodoal-Maiandeua, Pará, Brazil. 31 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto39-47. 384 records from (Supplement Table) Individual body mass, flipper length, oxidative balance indices and telomere length of king penguin chicks (Aptenodytes patagonicus) at the beginning of the post-winter growth. 2 records from The Persian / Arabian Gulf's sole great white shark Carcharodon carcharias (Lamniformes: Lamnidae) record from Kuwait: misidentification of a sandtiger shark Carcharias taurus (Lamniformes: Odontaspididae).. 2402 records from Census of plant species in Bonou forest reserve (Southern Benin). 15 records from Projeto Abrace o Boto Cinza. 2322 records from (Table AT8) Planktonic foraminiferal stratigraphy of ODP Hole 182-1134A. 77152 records from Conchological Society of Great Britain & Ireland - Mollusc (marine) data for Great Britain and Ireland. 7509 records from Perot Museum of Nature and Science. 21 records from Molecular phylogeny of Banza (Orthoptera: Tettigoniidae), the endemic katydids of the Hawaiian Archipelago. 64 records from Issumer Fleuth. 163 records from (Table 11) Relative frequencies of planktonic foraminifers and cluster arrangement of ODP Holes 127-794A and 127-197B. 13403 records from The Herpetology Collection at the Staatliches Museum für Naturkunde Stuttgart. 2 records from Beiträge zur Kenntnis bulgarischen Chilopoden. Teil V. Das Genus Polybothrus. 9349 records from Harriet Irving Botanical Gardens (HIBG). 177239 records from Inventaire National du Patrimoine Naturel : Données ONEMA sur les poissons et écrevisses d'eau douce.. 367 records from Clyde River Foundation - Twaite Shad (Alosa fallax) distribution for Scotland, historical to present. 2 records from Apistogramma eremnopyge, a new species of cichlid fish (Teleostei: Cichlidae) from Peru.. 1354 records from (Table 1) Planktonic foraminiferal communities at DSDP Holes 94-609B and 94-609. 7 records from Benthic hard-bottom communities abundance at X-Huinay in 2012. 444 records from Insect Collection from New Caledonia. 3 records from First report of the genus Conostigmus Dahlbom (Hymenoptera: Ceraphronoidea: Megaspilidae) from India with description of a new species. 9396 records from RSPB - White-tailed eagle reintroduction in Scotland - Sightings data (RSPB/SNH). 12 records from Six new, unusually small ants of the genus Leptomyrmex (Hymenoptera: Formicidae).. 1 records from Revision der Ceratozetidae, 5. Ceratozetes thienemanni WILLMANN (Arach., Acari, Oribatei). 2560 records from (Table T2) Planktonic foraminifera stratigraphy of ODP Hole 198-1211C sediments. 959 records from RSPB - Black-throated diver national surveys in Scotland (SCARABBS). 4447 records from Lepidoptera (Observations). 8 records from New species of the catfish genus Trichomycterus (Siluriformes, Trichomycteridae) from the headwaters of the rio São Francisco basin, Brazil.. 1715 records from (Appendix) Planktonic foraminifera abundances in ODP Site 138-847B. 372 records from Colección de Entomología - Arthropoda. 43480 records from UFP - Herbário UFP - Geraldo Mariz. 3447 records from Colección de Ornitología - Museo de Ciencias Naturales de La Salle. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Hoehlen. 2212 records from RIVM (NL) - Earthworm Observations in Soil Samples. 3182 records from Finnish Entomological Database: Heteroptera. 55 records from (Table 3) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840B. 9216 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Diptera_Tipulidae_NL. 678 records from (Table 2) Planktonic foraminiferal abundances in samples spanning the first appearance datum Globorotalia inflata at DSDP Hole 80-548. 654 records from Helgeland Museum, Tabanidae. 99 records from French national collection of Solanum tuberosum. 68 records from (Table 8) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-851B. 94709 records from Merseyside BioBank - North Merseyside Flowering Plants (unverified). 1 records from Beitrag zur Kenntnis der Höhlen-Oribatiden der Schweiz (Acari: Oribatida) (Neue und interessante Milben aus dem Genfer Museum LI). 47499 records from Sphaeroceridae Collection. 1706 records from University of Amsterdam (NL) - Páramo pollen reference collection. 531 records from Fish biodiversity of the Vitória-Trindade Seamount Chain, Southwestern Atlantic: an updated database. 61 records from Registros restauración ecológica- Magdalena medio. 8 records from Three new species of seasonal killifishes of the Simpsonichthys antenori species group (Teleostei: Cyprinodontiformes: Rivulidae) from the rio São Francisco basin, Brazil.. 77 records from Empria and Monsoma in Japan. 1490 records from (Appendix) Benthic foraminifera in early Eocene sediments of DSDP Hole 48-401. 10 records from Distribution and habitat of the Laotian Rock Rat Laonastes aenigmamus Jenkins, Kilpatrick, Robinson & Timmins, 2005 (Rodentia: Diatomyidae) in Vietnam. 195719 records from Colección Herbario Federico Medem Bogotá - FMB. 2 records from First record of Orobdella kawakatsuorum (Hirudinida: Arhynchobdellida: Erpobdelliformes) from Kunashir Island, Kuril Islands. 20 records from Lerchenauer Baggersee (München). 11518 records from Merseyside BioBank - North Merseyside Insects (verified). 99463 records from NPL collections. 5 records from Oribatid mites from Switzerland, IV (Acari: Oribatida: Suctobelbidae). 2608 records from Relative abundances of benthic foraminifers of sediment core Svanic90_9004. 599260 records from FLORIVON. 24657 records from Palaeobiology - Vertebrate Fossils Collection - Non Mammalia - Royal Ontario Museum. 198502 records from Reptiles and Amphibians collection (RA) of the Muséum national d'Histoire Naturelle (MNHN - Paris). 2090 records from Crustáceos de la Colección de Referencia de Biología Marina de la Universidad del Valle (CERBMcr-UV). 2174 records from MLZ Mammal Collection (Arctos). 12 records from (Table 1) Length, weight, fat content and age of Norwegian spring spawning herring (Clupea harengus) during 2007. 50317 records from MSU Mammalogy, Ornithology and Vertebrate Paleontology Collections. 225 records from Meiobenthos of target sites of Crimea in 2009/2010. 36974 records from Environment Agency - Environment Agency Rare and Protected Species records v1. 140 records from (Appendix) Stable carbon and oxygen isotopes, and Mg/Ca ratios of foraminifera from ODP Hole 154-925A. 38 records from The Oriental species of the ant genus Probolomyrmex (Insecta: Hymenoptera: Formicidae: Proceratiinae).. 7 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Melanopareiidae. 23 records from (Table 2) Live (stained) benthic foraminifera from stations in the northern Gulf of California. 105 records from People's Trust for Endangered Species - Noble Chafer: Pre-BAP records prior to 1998. 111802 records from Highland Biological Recording Group - HBRG Insects Dataset. 6855 records from Echinoderm collection of National Museum of Nature and Science. 124 records from (Appendix A1) Cenomanian benthic foraminifera of ODP Hole 207-1258A. 618 records from RSPB - Scottish Crossbill National Survey in the UK in 2008 (SCARABBS). 1854895 records from Vascular plants in Denmark recorded under the The Nationwide Monitoring and Assessment Programme for the Aquatic and Terrestrial Environments (NOVANA). 14 records from Inventario Herpetológico Pauto J, Rincón del Soldado, Yopal, Casanare. 4490 records from Colección Herpetológica del Museo Nacional de Historia Natural de Chile. 88263 records from URM - Herbário Pe. Camille Torrand. 19127 records from Biological Records Centre - Cerambycidae Dataset. 157869 records from Lund Museum of Zoology - Insect collections (MZLU). 1210 records from Abundance of megabenthic species in trawl catches per station in addition to table 2 during POLARSTERN cruise ARK-VIII/2 (EPOS). 1 records from Zooplankton abundance measured on water bottle samples during Jan Mayen cruise JM7. 80 records from Lahnufer in Villmar. 218 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 2000-2004. Part 2. 409 records from Iberian Peninsula and Balearic Island Bathynellacea (Crustacea, Syncarida) database. 198 records from Segunda caracterización biológica de hormigas cazadoras del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 1 records from On the morphology, biometry and biogeography of Lamtopyxis callistoma ( Amoebozoa : Arcellinida ). 318 records from A taxonomic review of the genus Azteca (Hymenoptera: Formicidae) in Costa Rica and a global revision of the aurita group.. 7671 records from HERBAM - Herbário da Amazônia Meridional. 2 records from Adetomyrma, an enigmatic new ant genus from Madagascar (Hymenoptera: Formicidae), and its implications for ant phylogeny.. 19 records from Record of 7 acritarch taxa from the Miocene, Pliocene and Pleistocene of ODP Hole 151-910C. 38200 records from Herbario Universidad de Antioquia (HUA). 93 records from (Table 5) Oligocene to Pleistocene nannofossil range chart for ODP Hole 134-829A. 20 records from (Table 2) Counts of live (stained) benthic foraminifera from stations in the northern Gulf of California. 26 records from A new species of Chondrostoma Agassiz, 1832 (Cypriniformes: Cyprinidae) with sexual dimorphism from the lower Rio Tejo Basin, Portugal.. 68304 records from IICT Herbário LISC. 634257 records from Inventario Español de Especies Terrestres (MAGRAMA). 1 records from Hoplophora decumana. 1562 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2011. 4373 records from Colección del Herbario de la Universidad Tecnológica del Chocó. 7873 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Himalayan Balsam Surveys (WT) - 2010-2012. 358 records from (Appendix D) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Site 161-975. 807 records from National Trust for Scotland - NTS Properties Sensitive Species Records 1800-2013. 103310 records from Plant Specimen from Herbarium (CDBI) in China, Chengdu Institute of Botany, Chinese Academy of Sciences. 6 records from (Table 3) Middle Eocene silicoflagellates from DSDP Hole 95-613. 24 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2003. 28 records from RSPB - Black grouse lek survey in Moray and Nairn 2009 (RSPB). 3 records from New data of three rare belondirid species (Nematoda, Dorylaimida, Belondiridae) from Vietnam, with the first record and description of the male of Oxybelondira paraperplexa Ahmad & Jairajpuri, 1979. 96 records from Trichoptera (caddisflies) of Ireland. 30 records from Lacantunia enigmatica (Teleostei: Siluriformes) a new and phylogenetically puzzling freshwater fish from Mesoamerica.. 40 records from Inventario de Herpetología en el Área Sujeta a Acuerdos de Conservación Voluntaria Quebrada Aguazula, Rincón del Soldado, Yopal. 601 records from Dinoflagellate cyst species of sediment core GeoB10732-3. 70738 records from University of Alberta Vascular Plant Herbarium (ALTA). 3 records from On two Italian Lithobius species described by Silvestri, with taxonomic notes on the genus Eupolybothrus Verhoeff (Chilopoda, Lithobiida). 4501 records from Colección de Mamíferos del Centro Nacional Patagónico. 367 records from Longhorn and buprestid beetles (Coleoptera: Cerambycidae, Buprestidae) of the forest-steppe “Bielinek” reserve and its surroundings. 73 records from (Table 7) Abundance of silicoflagellates and ebridians in selected samples from ODP Hole 138-850B. 1 records from On centipedes (Chilopoda) of Albania, 2. 3 records from Note su alcune specie di chilopodi della regione palestinese. 1 records from Myriopoden von Kreta, nebst Bitraegen zur allgemeinen Kenntnis einger Gattungen. 1 records from Estudio de los frutos y semillas del género Chenopodium en la Argentina. 24 records from Caenotropus schizodon, a new chilodontid fish from the Rio Tapajos drainage, Brazil (Ostariophysi: Characiformes: Chilodontidae).. 370 records from Collection Crustacea - KAUMM. 50 records from Description of Notarius biffi n. sp. and redescription of N. insculptus (Jordan and Gilbert) (Siluriformes: Ariidae) from the eastern Pacific, with evidence of monophyly and limits of Notarius.. 90 records from Taxonomy of the plesiolebiasine killifish genera Pituna, Plesiolebias and Maratecoara (Teleostei: Cyprinodontiformes: Rivulidae), with descriptions of nine new species.. 44 records from Solanum_baretiae. 7479 records from BioGIS - Vascular plants - Israeli Gene Bank. 412 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001E. 4 records from A third species in the rare Australian ant genus Peronomyrmex Viehmeyer (Hymenoptera: Formicidae).. 76 records from (Fig. 2) Vertical density profiles of meiofauna taxa in surface sediments of Potter Cove, King George Island, Antarctic Peninsula. 6730 records from National Museum of Marine Biology and Aquarium. 69982 records from Lepidoptera collection, Natural History Museum, University of Oslo. 3647557 records from Florabank1 - A grid-based database on vascular plant distribution in the northern part of Belgium (Flanders and the Brussels Capital region). 2 records from On the female of Gypona reversa DeLong & Martinson, 1972, with emphasis on genital structures (Insecta: Hemiptera: Cicadellidae). 106 records from (Appendix II) Foraminifera abundance in DSDP Hole 22-214. 13086 records from Collection of Coleoptera. 1 records from Hoplophora ardua. 3257 records from fundiv france database. 24 records from Sphodromantis viridis (Forskal, 1775): New for Portugal and new records of the rare and small mantids Apteromantis aptera (Fuente, 1894) and Perlamantis allibertii Guérin-Méneville, 1843 in the country (Mantodea: Mantidae and Amorphoscelidae). 7458 records from Colección de Reptiles del Instituto Alexander von Humboldt. 3 records from Selenops muehlmannorum spec. nov. from Southern Laos (Araneae: Selenopidae). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 61981 records from Stuart M. Fullerton Collection of Arthropods (UCFC), University of Central Florida. 13993 records from Herpetology. 1197 records from North Atlantic (Rockall Plateau) coccolith assemblage data for MIS 5 of ODP Hole 162-980B. 91 records from Zooplancton de sistemas acuáticos artificiales y naturales de Colombia. 60710 records from Leicestershire and Rutland Environmental Records Centre - Leicestershire & Rutland Coleoptera. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 146 records from A taxonomic revision of the catshark genus Poroderma Smith, 1837 (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 4944 records from Inventaire National du Patrimoine Naturel : Flore de l'Ain. 1 records from Cepheus latus. 179 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cuculidae. 253095 records from Lyman Entomological Museum (LEMQ). 1 records from Pelops torulosus. 9 records from Inventario Herpetológico Pauto M, La Primavera, Yopal, Casanare. 17802 records from The Bat Conservation Trust - Colony Count Survey. 10 records from Eupolybothrus cavernicolus Komerički & Stoev sp. n. (Chilopoda: Lithobiomorpha: Lithobiidae): the first eukaryotic species description combining transcriptomic, DNA barcoding and micro-CT imaging data. 173415 records from Hymenoptera specimen database of Kyushu University. 663 records from Colección de Aves Museo Universitario de la Universidad de Antioquia. 45159 records from VIS - Fishes in estuarine waters in Flanders, Belgium. 1 records from Oribates picipes. 1 records from Arthropoden aus südostalpinen Höhlen.. 202 records from BTCV Scotland - BTCV wildlife counts recording workshops. 26847 records from Merseyside BioBank - North Merseyside Other Taxa (unverified). 5053399 records from Southern African Bird Atlas Project. 38 records from Fourteen new species of Pseudisobrachium (Hymenoptera, Bethylidae) from Atlantic rain forest of Espírito Santo, Brazil.. 2576 records from Hosted Invertebrate Collection 01. 96 records from (Table T4) Biogenic and mineral composition of sediments cored in Hamburg-Langenhorn. 39 records from University Marine Biological Station Millport - 1995 EC Study Contract Clyde Sea Nephrops Stock Assessment Study. 9054 records from The Scottish Ornithologists' Club - Highland bird data 2002 - 2003 - non-breeding records. 1 records from Dolistenus menozzii n. sp. della famiglia Platydesmidae (Miriapodi Colobognati); e altri miriapodi della Calabria. 16826 records from Tachinid Recording Scheme - Tachinid Recording Scheme - GB and Ireland records. 5 records from Ventichthys biospeedoi n. gen. et sp. (Teleostei, Ophidiidae) from a hydrothermal vent in the South East Pacific.. 4 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2012. 63 records from (Data S1) Palynology of ODP Site 119-739. 4857 records from University of Alberta Museums, Entomology Collection. 48 records from Heider Bergsee (Brühl). 1349 records from Caracterización florística y estructura de los relictos de bosque seco tropical en el bajo Cauca, jurisdicción Corantioquia. 52 records from Isotope tracer experiment: meiofauna counts. 1722 records from Cambridgeshire & Peterborough Biological Records Centre - Orthoptera dataset held by CPERC. 1371 records from (Table T2) Abundance of dinoflagellates and other palynomorphs in Eocene-Oligocene sediments from ODP Hole 189-1172A. 24855 records from Georgia Southern University - Savannah Science Museum Herpetology Collection. 259 records from (Table 7) Benthic foraminifera genera assemblage at DSDP Section 80-548A-22. 374 records from published_chenopodium_vulvaria_observations. 17 records from Bridging the distributional gap of Tylorida striata (Thorell, 1877) and new synonymy (Araneae: Tetragnathidae). 18 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0001I. 1 records from Pollen analysis of sediment profile KAIX_A from Kaiserwinkel. 10 records from schlittschuhweiher. 585 records from Ascomycetes of Russian Fennoscandia. 7403 records from Freshwater fishes of Hidalgo state (Mexico) in the MZNA fish collection of the University of Navarra (Spain). 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 41 records from Studies on the Zoarcidae of the southern hemisphere. X. New records from western Antarctica.. 4 records from (Table 3) Mean plasma lipid content, and plasma PCB and OH-PCB concentration of polar bear (Ursus maritimus) mothers and cubs. 552 records from (Table 2) Relaticve abundances of Eocene to Oligocene planktonic foraminifera in ODP Hole 135-841B. 130059 records from Inventaire National du Patrimoine Naturel : Mammifères de France. 1 records from A record of Anzygina billi Fletcher & Larivière, 2009 (Hemiptera: Cicadellidae) from New Zealand. 8880 records from Actualisation de la cartographie des Ptéridophytes de France et d'Europe occidentale. 582 records from Bioblitz 2013 Copenhagen Denmark. 26152 records from Herts Bird Club - Hertfordshire Breeding Bird Atlas : 1967-1973. 5850 records from UAFMC Fish. 119366 records from The digitization of plant specimens of NTU. 1 records from Taenioides kentalleni, a new species of eel goby from Saudi Arabia (Gobiidae: Amblyopinae).. 15934 records from Mamíferos de la colección del Instituto Alexander von Humboldt. 31 records from Alobevania, a new genus of neotropical ensign wasps (Hymenoptera: Evaniidae), with three new species: integrating taxonomy with the World Wide Web.. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 1573019 records from SA Flora (BDBSA). 74208 records from NCSM Fishes Collection. 9173 records from Colección de líquenes del Herbario "Jaime Andrés Rodríguez". LEB-Lichen. 19 records from (Table 1) Abundance of unicellular eukaryotes in ice cores collected during the July 2008 CCGS Amundsen cruise in Darnley Bay. 77 records from Xiphosura collection of National Museum of Nature and Science. 360 records from (Figure 1g) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3174. 365 records from Colección Herpetológica de la Patagonia. 18 records from First report of Dicopus longipes (Subba Rao) (Hymenoptera: Chalcidoidea) from India with new distribution data on some species. 57879 records from Albany Museum Grant. 1004 records from Aix-Marseille Université - MARS herbarium – Cytogenetic data-base. 62099 records from Marine Biological Association - DASSH Data Archive Centre Academic surveys. 34502 records from Merseyside BioBank - North Merseyside Birds (verified). 26 records from Myoglanis aspredinoides (Siluriformes: Heptapteridae), a new catfish from the Río Ventuari, Venezuela.. 1323 records from (Table 10) Benthic foraminifera in late Miocene sediments of DSDP Hole 90-591. 5368 records from Dutch Mammal Society (NL) - Mammal observations extracted from historic reports. 471 records from Aschelminth collection of National Museum of Nature and Science. 24694 records from Amphibian Specimens. 5 records from Chromosome studies in the aquatic monocots of Myanmar: A brief review with additional records. 51900 records from Thames Valley Environmental Records Centre - Local Wildlife Site Surveys Berkshire. 1481 records from Reptilia notes, NTNU, Trondheim. 2082 records from Vietnam Type Culture Collection. 1 records from On the Chilopoda from Turkey. 2 records from Odontamblyopus rebecca, a new species of amblyopine goby from Vietnam with a key to known species of the genus (Gobiidae: Amblyopinae).. 31 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1998. 63 records from Polypterus mokelembembe, a new species of bichir from the central Congo River basin (Actinopterygii: Cladistia: Polypteridae).. 88018 records from NINA Vanndata øvrige arter. 36 records from New ants (Hymenoptera: Formicidae) from Micronesia.. 3567 records from Hymenoptera collection (EY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 538 records from Recent noteworthy findings of fungus gnats from Finland and northwestern Russia (Diptera: Ditomyiidae, Keroplatidae, Bolitophilidae and Mycetophilidae). 6997 records from CHAS Vertebrates. 455 records from (Table T2) Calcareous nannofossil abundance across the Oligocene/Miocene boundary of ODP Hole 189-1168A sediments. 2848 records from Kangawalla Bird Sightings. 175 records from (Table 6) Benthic foraminifera genera assemblage at DSDP Section 80-548A-16-3. 71 records from RSPB - Bringing Reedbeds to Life Water Vole and Mink Survey of five key reedbed sites in England in 2009, 2010.. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario ICESI. 110017 records from Louisiana State University Herbarium. 303 records from The South American annual killifish genus Austrolebias (Teleostei: Cyprinodontiformes: Rivulidae): phylogenetic relationships, descriptive morphology and taxonomic revision.. 56 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Alcedinidae. 841 records from Dorset Environmental Records Centre - Dorset Invasive Alien Plants - NBN South West Pilot Project Case Studies. 11 records from Pollen profile from sediment core AV14_K2-4. 1408 records from (Table 2) Distribution of Campanian-Maestrichtian agglutinated foraminifers in DSDP Hole 78-543A. 200 records from (Table T1) Neogene stratigraphy of diatoms, ebridians and endoskeletal dinoflagellates in ODP Hole 183-1138A. 1627 records from RSPB - Bird survey records from RSPB's London House Sparrow Parks Project 2009-2010, covering 19 London parks and surrounding streets (Funded by SITA Trust,. 745 records from (Table 2) Benthic foraminifers at DSDP Hole 72-518. 4286 records from Inventaire National du Patrimoine Naturel : Atlas de la flore de Lorraine. 380 records from (Table 4) Benthic foraminiferal genera in DSDP Core 95-612-16 and 95-612-17. 355 records from Culture Collection of Cryophilic Algae. 2 records from Note tassonomiche e faunistiche su Chilopodi della Grecia (Chilopoda). 767 records from BioGIS - Bats - Asaf Tsoar database. 3 records from A new species of the Asian catfish genus Pseudolaguvia from Myanmar (Teleostei: Ostariophysi: Siluriformes: Erethistidae).. 19309 records from Mammal collection, Natural History Museum, University of Oslo. 12512 records from ULg_Hexapoda. 2880 records from Coleoptera, NEF. 223433 records from Phytochorologie des départements français. 10 records from Devon Biodiversity Records Centre - Devon giant hogweed data 1997 to 2000. 5872 records from EcoRecord - Beetle (Coleoptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 73 records from Revision of the ant genus Streblognathus (Hymenoptera: Formicidae: Ponerinae).. 2297 records from Joint Nature Conservation Committee - England Otter Survey Database. 46 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM2. 2000 records from Colección Científica de Referencia Zoológica del Chocó- Herpetología. 3956 records from SMDB - Santa Maria Departamento de Biologia. 2782 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Taminango, Nariño. 21 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Rynchopidae. 213760 records from HUEFS - Herbario da Universidade Estadual de Feira de Santana. 9 records from Peyerimhoffia jaschhoforum (Diptera, Sciaridae), a new deadwood inhabiting species from Canada. 6 records from First description of the male caste of the Himalayan endemic ant Lasius alienoflavus Bingham, 1903 (Hymenoptera: Formicidae), with re-description of the female and queen castes . 6 records from On a new species of the genus Moenkhausia Eigenmann (Ostariophysi: Characidae).. 27 records from RSPB - Bearded Tit National Survey in Britain 1992 (SCARABBS). 32 records from (Table T1) Calcareous nannofossil abundance of ODP Hole 189-1168A sediments. 45 records from Scottish Natural Heritage - Surveys of Najas flexilis (Slender naiad) in Scotland 2004 â 2011. 327 records from (Table 1) Fossil record of foraminifera and ostracoda from Albersdorf clay pit, north Germany. 2802 records from Merseyside BioBank - North Merseyside Fish (unverified). 496 records from Colección Entomológica del Centro Nacional Patagónico “Francisco P. Moreno” (CNP-CE). 373 records from Dinocyst occurrences and zonations from IODP Hole 313-M0029A. 27 records from A new species of Astyanax (Teleostei, Characiformes, Characidae), with breeding tubercles, from the Paraná and Uruguay river basins.. 9248 records from UAM Fish Collection (Arctos). 766 records from Antarctic Porifera database from the Spanish benthic expeditions: Bentart, Gebrap and Ciemar. 81388 records from natagora-earlybirds. 52 records from The Myrmica punctiventris and M. crassirugis species groups in the Nearctic region.. 15630 records from Vertebrats d'Andorra. 964 records from Arachnida del Museo de Entomología de la Universidad del Valle. 7 records from Calvia explanata sp. n. (Coleoptera: Coccinellidae: Coccinellinae) from the Indian Subcontinent. 2448 records from (Table T2) Abundance of stratigraphically important planktonic foraminifera in ODP Hole 186-1151A sediments. 15 records from (Table 1) Occurrence and abundance of late Early Cretaceous radiolarians at DSDP Hole 62-463. 397 records from Danish Lacewings (Neuroptera). 50 records from (Table 1) Biometrics of five seabird species from Kongsfjorden, Svalbard. 2824 records from Fundación Miguel Lillo - Colección Invertebrados. 712 records from Scorpiones collection (RS) of the Muséum national d'Histoire naturelle (MNHN - Paris). 756 records from Targeting a portion of central European spider diversity for permanent preservation. 216 records from (Table T1) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1135A. 42861 records from DMNS Bird Collection (Arctos). 3688 records from Clare Biological Records Centre dataset. 3945 records from TTRS Ornithology. 752 records from The Fish Collection at the Zoologische Staatssammlung München. 32 records from Archaea Collection in BCRC. 1 records from Zetes rubens. 108 records from Studies in Hawaiian Diptera I: New Distributional Records for Endemic Asteia (Asteiidae). 65486 records from Herbier Louis-Marie (QFA) - Collection de plantes vasculaires. 1364 records from Irish Collembola records. 72237 records from Vascular plant herbarium, Agder naturmuseum og botaniske hage. 19237 records from Alterra (NL) - Biological Indicator Soil Quality-Microarthropods inventory in different habitats. 76 records from Schulgelände des Gymnasiums Nepomucenum (Coesfeld). 2 records from Ituglanis paraguassuensis sp. n. (Teleostei: Siluriformes: Trichomycteridae): a new catfish from the rio Paraguacu, northeastern Brazil.. 2 records from Arthropoden aus südostalpinen Höhlen.. 12434 records from Museu Paraense Emilio Goeldi - Coleoptera Collection. 918 records from Caracterizaciones rápidas de biodiversidad en grupos biológicos de la planicie del valle del río Cauca. 1131 records from (Table T8) Planktonic foraminifera stratigraphy of ODP Hole 198-1210A, Zone P4. 1 records from Nothrus pollinosus. 6 records from (Table 5) Miocene biostratigraphy of the Langenfeldian and Gramian stages in Schleswig-Holstein. 9879 records from Bibliographic records of Angola mammals. 11 records from (Table AT2) Petrology in point counts of ODP Hole 210-1276A, two ODP Leg 173 sites and DSDP Hole 47-398D. 21704 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Netherlands. 98423 records from Insect species recorded in sugarcane fields of Khon Kaen Province, Thailand, over three seasons in 2012. 139 records from Nematode abundances in sediments from the Håkon Mosby Mud Volcano (HMMV) obtained during expeditions with Polarstern and Pourquoi Pas ?. 240 records from Saproxylic beetles of the Po plain woodlands, Italy. 1049 records from Colección de Crustáceos Decápodos y Estomatópodos del Centro Oceanográfico de Cádiz: CCDE-IEOCD. 26624 records from Monitoring data from the federal state Bavaria (Germany). 2 records from (Supplement Table 3) Percentage cover abundance of plants recorded at the Fell-field Site on Disko Island. 197 records from Inventaire National du Patrimoine Naturel : CBN Aquitaine-Poitou-Charentes. 98 records from RSPB - Twite national sample survey in the UK in 1999 (SCARABBS). 857 records from Field Study Group of the Dutch Mammal Society (NL) - 2004 - Mammal Survey Rakitovec, Slovenia. 255 records from GENT Lactarius Deliciosi. 1 records from Myriopoden von Epirus. 39035 records from Merseyside BioBank - North Merseyside Birds (unverified). 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 8 records from (Table 2) Monthly statistics of king penguin (Aptenodytes patagonicus) colony arrivals, Possession Island. 176 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2010. 52 records from CIM Specimens. 8 records from (Table 1) Trawled distance, Isopoda per 1000 m haul length, expected number of species, evenness, and the Shannon-Wiener index during POLARSTERN cruise ANT-XIX/3 (ANDEEP I). 102 records from Sipuncula collection of National Museum of Nature and Science. 588 records from Relative abundance of ostracods in sediment core Lz1120. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 8 records from (Table 3) Characteristics of the Chamelea gallina population on the beach of the Anapa Bay Bar in October 2010. 189 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Threskiornithidae. 520 records from Lepidoptera collection (EL) of the Muséum national d'Histoire naturelle (MNHN - Paris). 68 records from Late Pleistocene planktonic foraminifera of Hole 302-M0004C (Addendum 1). 7 records from First record of the male of the widespread Calliscelio elegans (Perkins) (Hymenoptera, Platygastridae) along with some taxonomic notes on the species. 808 records from Greater Manchester Ecology Unit - Distribution of Great Crested Newts in Greater Manchester. 2654 records from Collection of Hymenoptera. 5 records from Specimen records associated with "A troglomorphic spider from Java (Araneae, Ctenidae, Amauropelma). 6083 records from Biological Records Centre - Sepsidae (Diptera) records from Britain and Ireland to 1985. 1 records from Nothrus pigerrimus. 17 records from (Table A) Fauna associated with Bathymodiolus azoricus mussel beds within the Menez Gwen hydrothermal field, Mid-Atlantic Ridge. 9997 records from Myriapoda & Onychophora collection (MY) of the Muséum national d'Histoire naturelle (MNHN - Paris). 33 records from Relative abundance of Florisphaera profunda in ODP Hole 121-758C. 1 records from Oppiella signata, eine neue Art der Familie Oppiidae aus dem Osterzgebirge (Acari, Oribatei). 1287 records from RAVON (NL) - Fish observations extracted from Hoek (1888) and Hoek (1897). 156 records from Schizomida Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 51933 records from CESJ - Herbário Leopoldo Krieger. 202 records from Uncorrected Mg/Ca and sea surface temperature data for Site 165-1000. 968 records from (Table T1) Planktonic foraminifera stratigraphy of ODP Hole 198-1209A, Zones Palpha-P3b. 35 records from Hertfordshire Biological Records Centre - Hertfordshire Otter Records 2002 - 2012. 45 records from Sediment age, abundance of planktonic foraminifera shells, degree of their dissolution, percentage of benthic foraminifera in total foram fauna, Core GC-11, Sea of Okhotsk. 5569 records from HBRA - Herbário do Instituto de Estudos Costeiros da Universidade Federal do Pará. 43 records from (Table 3) Relative abundance of Azolla spp., peridinoid dinocysts, gonyaulacoid dinocysts, non-saccate pollen, bisaccate pollen and spores from the Lomonosov Ridge during different Arctic coring expeditions. 13717 records from OUPR - Herbário "Professor José Badini". 92 records from (Appendix) Diversity indices of benthic foraminiferal fauna of DSDP Hole 48-401. 8 records from Five new species of the damselfish genus Chromis (Perciformes: Labroidei: Pomacentridae) from deep coral reefs in the tropical western Pacific.. 45 records from Phytoplankton abundance measured on water bottle samples during Jan Mayen cruise JM1. 568 records from (Appendix 2) Calcareous nannofossils in ODP Hole 189-1172A. 76 records from (Appendix A2) Calcareous nannofossil counts of ODP Site 207-1260. 583 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-847B. 50 records from A survey of the family Carabodidae C. L. Koch, 1836 (Acari: Oribatida). 644 records from (Table T1) Planktonic foraminiferal stratigraphy of ODP Hole 173-1065A sediments. 132 records from (Table T2) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049B. 1581 records from Colección Ornitológica de la Universidad Industrial de Santander. 1557 records from Hypogean Crustacea recording scheme - Hypogean macro-Crustacea records. 5 records from A new species of Notarius (Siluriformes: Ariidae) from the Colombian Pacific.. 372 records from El efecto de la variación ambiental en la diversificación de anfibios y la prevalencia de su patógeno mortal: Un transecto por los humedales desde el Magdalena Medio hasta la Orinoquía. 58 records from Mamíferos laguna El Tinije. 1 records from Études myrmécologiques en 1886.. 15879 records from HAMAB - Herbário Amapaense. 21760 records from CUMV Mammal Collection (Arctos). 289 records from (Appendix B) Nannofossil abundance in ODP Hole 165-998A sediments. 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 5 records from (Table 2) Osmium isotope ratios and Re-Os element content for cleaned and uncleande foraminifera of ODP Hole 121-758A. 155 records from Megophthalmidia_of_North_America. 7208 records from Royal Horticultural Society - Records from the RHS insect reference collection. 53 records from Royal Horticultural Society - Wisteria scale (Eulecanium excrescens) records acquired by the Royal Horticultural Society. 27167 records from Bird tissue collection, Natural History Museum, University of Oslo. 382 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Scolopacidae. 9 records from "Ach, du dicke Eiche", Wald an der Oste-Grundschule Heeslingen. 499 records from (Table 2) Biostratigraphy of marine benthic and planktonic taxa in sediment core GIK14350 near Dagebüll, northern Germany. 1894 records from Aves Playeras y Otras Aves Asociadas a Arrozales en los Departamentos de Casanare y Meta en 2009 - 2010. 30 records from (Table 1) Carbonate constituents and quartz in the sand-sized fraction in Mississippi Fan sediments, DSDP Hole 96-615. 11731 records from HAS-Algae - Coleção Ficológica do HAS. 32962 records from Colección Nacional de Aracnología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 1246 records from (Table 2) Relative abundances of benthic foraminifera in ODP Hole 128-798B. 2 records from Lubbockichthys myersi, a new species of dottyback fish from Guam (Pseudochromidae: Pseudoplesiopinae).. 7410 records from Helgeland Museum, Lepidoptera. 710 records from Thames Valley Environmental Records Centre - Natural England Bat Records for Berkshire and Oxfordshire (Held by Thames Valley Environmental Records Centre). 151 records from Molluscan fauna of Gueishan Island of Taiwan. 820552 records from Fauna Atlas N.T.. 1470 records from Institut Menorquí d'Estudis. Herbarium Generale Minoricae: HGM. 1080 records from (Appendix) Foraminifer abundance of a volcaniclastic interval from ODP Hole 197-1206A. 1 records from Zetes ephippiatus. 1 records from Zetes fuscomaculatus. 108 records from (Table 5) Live benthic foraminifera in sediment core SO130-236MC. 924 records from (Table 15) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-592. 2 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 48 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1209A. 90399 records from CUMV Fish Collection (Arctos). 6065 records from LISU Herbario Angola. 3 records from (Table 2) Upper Eocene silicoflagellates from DSDP Hole 95-612. 6 records from A new Savignia from Cretan caves (Araneae: Linyphiidae). 12109 records from Inventario de fauna presente en la jurisdicción de Corantioquia. 29263 records from Tromsø Museum, Fungi. 122409 records from UAM Mammal Collection (Arctos). 12 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 1996. 3904981 records from FlorKart - FlorenKartierung Gefaesspflanzen. 496530 records from Field Museum of Natural History (Zoology) Bird Collection. 47 records from Three new Parananochromis species (Teleostei, Cichlidae) from Gabon and Cameroon, Central Africa.. 1138 records from (Table T2) Benthic foraminfera stratigraphy of ODP Hole 199-1220B sediments. 11 records from A new species of Hemigrammus Gill, 1858 (Characiformes: Characidae) from Rio Caura, Venezuela.. 12 records from (Table 1) Sex, age and numbers of polar bear skulls (Ursus maritimus) collected in Svalbard. 301 records from Revision of Archaeoteleia Masner (Hymenoptera: Platygastroidea, Scelionidae).. 1948 records from CCBER Mammalogy Collection. 1 records from Die vom k. k. Oberartze Herrn Dr. Justyn Karlinski im Jahre 1887 in Bosnien, der Herzegowina und in Novibazar gesammelten Myriopoden. 479 records from (Table 3) Benthic foraminiferal distribution at ODP Site 127-797. 93276 records from Merseyside BioBank - North Merseyside Flowering Plants (verified). 2476 records from EcoRecord - Bug (Hemiptera) Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 13 records from Taxonomy of European Damaeidae (Acari: Oribatida) III. Species of the Kunstidamaeus tenuipes (Michael, 1885) group, with a description of Kunstidamaeus fraterculus n. sp. from East Slovakia. 15597 records from Countryside Council for Wales - Skomer Marine Nature Reserve (MNR) Marine Monitoring Programme. 149 records from (Appendix A) Palynofacies raw counts of DSDP Hole 38-338. 4779 records from (Table S1) Benthic foraminifera of ODP Holes 199-1218A and 199-1219A. 6 records from Fundulopanchax kamdemi (Cyprinodontiformes: Nothobranchiidae) a new species from Korup National Park, western Cameroon.. 69 records from (Table 11) Distribution of coccoliths along Core AMK7-786 from the Tajura Rift. 136 records from Plants galls. 1 records from Die Myriopodenfauna von Albanien und Jugoslavien. 464 records from Lepidoptera collection, NTNU, Trondheim. 31000 records from Plant Specimen Database of Tama Forest Science Garden, Forestry and Forest Products Research Institute, Japan. 74752 records from Mammals collection (ZM) of the Muséum national d'Histoire naturelle (MNHN - Paris). 519292 records from Museum Victoria provider for OZCAM. 4 records from Pollen analysis of sediment profile PLU01 from Plussee. 2475 records from HSU Wildlife Eggs and Nests. 3359932 records from Dutch Foundation for Applied Water Research (STOWA) - Limnodata Neerlandica. 153 records from National Pine Marten Survey of Ireland 2005 - 2007. 2 records from Simpsonichthys suzarti sp. n. (Teleostei: Cyprinodontiformes: Rivulidae): a new annual fish from the Rio Pardo floodplains, northeastern Brazil.. 92 records from Bothrocara nyx: a new species of eelpout (Perciformes: Zoarcidae) from the Bering Sea.. 1 records from Pollen analysis of sediment profile BIB00 from Biber See. 948 records from Field Study Group of the Dutch Mammal Society (NL) - 2008 - Mammal Survey Muntii Padurea Craiului - Apuseni mountains, Romania. 1095 records from (Figure 3) Distribution of dinoflagellate cysts in the late Albian of DSDP Hole 79-547B. 6 records from MfN - Micropaleontology. 19 records from Counts of benthos communities in Kongsfjorden in 2009. 540 records from Countryside Council for Wales - CCW Freshwater Fish ad hoc Records for Article 17 Reporting. 40109307 records from Artdata. 13325 records from Herbier du Bénin. 2983 records from University of Amsterdam (NL) - Páramo vegetation research, Western Andean Cordillera. 161 records from Schulgelände Paul-Gerhardt-Schule-Dassel. 31 records from The identity of catfishes identified as Mystus cavasius (Hamilton, 1822) (Teleostei: Bagridae), with a description of a new species from Myanmar.. 20 records from Inventario Herpetológico EPF Floreña, Yopal, Casanare. 558 records from Studies in Hawaiian Diptera II: New Distributional Records for Endemic Scatella (Ephydridae). 32 records from A review of the subfamily Acaenitinae Förster, 1869 (Hymenoptera, Ichneumonidae) from Ukrainian Carpathians. 2577 records from Shellfish (WSHN-MS). 90 records from University of Amsterdam (NL) - Páramo Vegetation Research, paramo in the Sabana de Bogota area, Colombia. 9123 records from Flora of Słowiński National Park, Poland. 711 records from Odonata collection, NTNU, Trondheim. 2444 records from Colección de Algas del Herbario Nacional, Museo Nacional de Historia Natural de Chile. 246 records from (Table 2) Distribution of Cretaceous nannofossils at DSDP Hole 79-545. 3 records from A revision of the Neotropical spider genus Ancylometes Bertkau (Araneae: Pisauridae). 132 records from (Table 1) Relative abundances of benthic foraminifera in ODP Site 128-798C. 1698 records from RSPB - Red-throated diver national surveys in Scotland - raw data (SCARABBS). 541 records from (Table T6) Biostratigraphy of important benthic foraminifer taxa in sediments cored in Ratekau, Schleswig-Holstein. 3768 records from Eggs Specimen. 27 records from Lioscorpius trifasciatus, a new scorpionfish (Scorpaeniformes: Setarchidae) from the South-West Pacific Ocean.. 34609 records from Butterflies of Ireland. 960 records from (Table 4) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Site 167-1013 sediments. 3 records from Diatom abundance of Hole 38-338, Part 2. 2303 records from (Appendix) Dinoflagellate abundance in ODP Site 202-1233. 150 records from Abundance of phytoplankton, heterotrophic nanoflagellates and bacteria through the water column at time series station L4 in the Western English Channel in 2011. 8579 records from The atlas of breeding birds in Małopolska. 17 records from (Table T4) Calcareous nannofossil abundance of ODP Site 189-1171 sediments. 1612 records from (Figure 8b) Distribution of Cretaceous planktonic foraminifers, calpellionids and associated organisms from DSDP Hole 77-535. 540 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 16 records from (Table V) Distribution of diatoms in samples from Heidemann Valley trench, Antarctica. 1 records from Nouveautes sur la faune des Chilopodes de Yougoslavie. 6 records from Arthropoden aus südostalpinen Höhlen. 314 records from Peces laguna El Tinije. 1905 records from BioGIS - Reptiles - INPA database. 51748 records from Museu Paraense Emilio Goeldi - Ictiology Collection. 16 records from (Table 4) Abundance, preservation, and distribution of calcareous nannofossils in ODP Hole 135-840C. 27079 records from Colección de Aves de Colombia del Instituto Alexander von Humboldt. 22978 records from Humber Environmental Data Centre - Humber Environmental Data Centre - Non Sensitive Records from all taxonomic groups. 10 records from Revision der Ceratozetidae, 4. Ceratozetes mediocris Berlese (Arach., Acari, Oribatei). 282 records from Migratory shorebirds (sandpipers and plovers) in Hokkaido. 71 records from (Data S1) Palynology of ODP Site 113-696. 13413 records from Herbario Nacional de Plantas Celulares - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 2 records from A redescription of the species of Eupolybothrus Verhoeff s. str. preserved in the British Museum (Natural History) and the Hope departement of Zoology Oxford (Chilopoda Lithobiomorpha). 1803 records from Flora of tanzania. 16195 records from People's Trust for Endangered Species - Hedgehog records 2005-2006: Hogwatch and Rural Landowner surveys. 11729 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Hymenoptera_Bombidae_Types. 252 records from RSPB - Black grouse leks in the Forest of Clunie, 2002-2010 (RSPB, SNH). 11 records from (Figure 4) Distribution of late Paleocene calcareous nannofossils in ODP Hole 132-810C. 18940 records from Cowan Tetrapod Collection - Mammals. 767 records from Scottish Natural Heritage - Compilation of records of 12 Article 17 terrestrial mammal species in Scotland. 777 records from INRA-Versailles Arabidopsis natural variants. 75 records from New species of the Eastern Hemisphere genera Afroheriades and Noteriades (Hymenoptera, Megachilidae). 1476 records from Harvestmen_of_French_Guiana. 1 records from Nothrus convexus. 2 records from Parioglossus galzini, a new species of ptereleotrid dartfish from Rapa Island (Teleostei: Gobioidei: Ptereleotridae).. 10 records from New records of Microgaster deductor Nixon, 1968 (Hymenoptera: Braconidae: Microgastrinae) for the Holarctic region, with comments on its historical distribution. 9792 records from International Collection of Microorganisms from Plants - New Zealand National Microbial Collection. 2815 records from Helgeland Museum, Araneae. 4 records from A new carpenter ant, Camponotus parabarbatus (Hymenoptera: Formicidae) from India. 1129 records from Upper Silesian Museum, Insect Collection. 78915 records from Biological Records Centre - Grasshopper and Cricket (Orthoptera) and related species records from Britain and Ireland to 2007. 1702 records from (Table 1) Benthic foraminifera species observed in the Quaternary samples from DSDP Hole 95-612. 102 records from Review of the Nearctic genus Scyletria Bishop & Crosby (Araneae, Linyphiidae), with a transfer of S. jona to Mermessus O. Pickard-Cambridge. 2412 records from Ohio University Invertebrate Paleontology Collection. 1833 records from (Appendix) Benthic foraminifera distribution of upper Creatceous and Paleocene at DSDP Hole 72-516F. 1000 records from PSUZC-Amphibians Collection. 251744 records from Herbarium - Instituto Nacional de Pesquisas da Amazônia (INPA). 665 records from Nottinghamshire Biological and Geological Records Centre - Nottinghamshire Biodiversity Action Group Brown Hare Survey. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 11371 records from Herbario Museo de La Salle Bogotá (MLS). 164 records from John Muir Trust - Species Records for John Muir Trust Properties Nevis, Sandwood, Quinag and Schiehallion 2010.. 1323 records from Algae (KBRC-AG). 6 records from Total meiobenthos abundance from the Crimea shelf, Black Sea, area I. 91 records from European bison in Białowieża Primary Forest. 1 records from Nothrus canaliculatus. 2 records from Hornmilben (Oribatida) [pages 323 to 417]. 21 records from (Table 3) Pleistocene nannofossil range chart for ODP Hole 134-831A. 4996 records from Ohio State University Tetrapod Division - Amphibian Collection (OSUM). 78 records from (Table T1) Abundance of dinoflagellate cysts and other palynomorphs in ODP Hole 184-1148A. 63 records from Revision of the ant genus Myrmoteras in the Malay Archipelago (Hymenoptera, Formicidae).. 2868 records from Tree Diversity and Dynamics of the Forest of Seu Nico (Brazil/MG). 62015 records from Atlas of Iberian water beetles (ESACIB database). 554 records from Bioblitz 2014 Kalvebod Fælled, Denmark. 649 records from Countryside Council for Wales - Great Crested Newt (Triturus cristatus) Sites in Wales to 2003. 285 records from (Figure 7) Stratigraphic distribution of selected dinoflagellate species in DSDP Hole 93-603B. 138 records from (Table 1) Late Pleistocene planktonic foraminifera of Hole 302-M0004C. 1 records from Zetes latipes. 4 records from (Figure 10) Relative abundance of nannoliths at DSDP Hole 62-466. 270 records from Nematode abundance in cold seep sediments of the Nordic Margins (Nyregga, Styregga, Haakon Mosby Mud Volcano). 1023 records from Greater Manchester Ecology Unit - Invasive and Non-native Species From Greater Manchester. 40530 records from Escarabajos Coprófagos (Coleoptera: Scarabaeinae) de la Colección Entomológica del Instituto Alexander von Humboldt. 7756 records from HUFSJ - Herbário da Universidade Federal de São João del-Rei. 2172 records from Coleccin de Reptiles. 55056 records from Biological Records Centre - Reptiles and Amphibians Dataset. 11762 records from Chrysomelidae of the Carpathians. 233 records from (Table 3) Relative abundances of benthic foraminifera in chosen time-slices from cores obtained in the Nordic and Barents Seas. 994 records from (Appendix B) Dinoflagellate cysts in Southeast Pacific Ocean surface sediments. 1 records from On the Chilopoda from Turkey. 7 records from (Table 4) Characteristics of the Donax trunculus population on the beach of the Anapa Bay Bar in October 2010. 73 records from (Table 1) Distribution of Upper Cretaceous agglutinated benthic foraminifers in DSDP Hole 20-196. 1578 records from (Appendix B) Benthic foraminifera in Indian Ocean surface sediments. 3333 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campañas 2009-2010. 29 records from Potential indicator species of climate changes occurring in Québec, Part 1: the small brown lacewing fly Micromus posticus (Walker) (Neuroptera: Hemerobiidae). 2 records from Die Myriopodenfauna von Albanien und Jugoslavien. 23 records from Revision of the generic classification of the hawkfishes (Cirrhitidae), with descriptions of three new genera.. 284 records from Distribution of planktic foraminifera and stable istopes of sediment core MSM05/5_712-2. 11392 records from Danish Plant Bugs (Miridae). 3382 records from People's Trust for Endangered Species - Hedgehog Hibernation Survey records. 202 records from Inventario de Aves Buenos Aires, Tauramena, Casanare. 37820 records from Belgian Coccinellidae - Ladybird beetles in Belgium (INBO subset). 14 records from (Table 2) Abundance of metazoan ice meiofauna in the bottom 30 cm of level sea ice obatined during the 2005 Hidden Ocean expedition. 906 records from Digital Florula - Las Cruces Biological Station. 2217 records from Gothenburg Herbarium - Types (GBIF:IH:GB:Herbarium). 1 records from Celaeno spinosa. 300 records from (Table 3) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Coniacian-Santonian to Albian. 48 records from (Table T2) Biostratigraphy of calcareous nannofossil taxa in ODP Hole 183-1136A. 297 records from Clyde River Foundation - Bullhead (Cottus Gobio) distribution for Scotland, historical to present. 632 records from MVZ Hildebrand Collection (Arctos). 157237 records from Naturalis Biodiversity Center (NL) - Paleontology Invertebrates. 657 records from (Table 2) Abundance of Miocene to Pleistocene dinoflagellate cysts in ODP Site 133-823. 3 records from Redescription of Lystrocteisa Simon, 1884 (Araneae: Salticidae) from New Caledonia. 24121 records from Endemic plants of the Congo basin. 3 records from Collection Crustacea - ZSRO. 119 records from Various insect orders, NEF. 27988 records from Inventaire National du Patrimoine Naturel : Loup en France. 584476 records from Joint Nature Conservation Committee - Marine Nature Conservation Review (MNCR) and associated benthic marine data held and managed by JNCC. 138472 records from Inventaire National du Patrimoine Naturel : Flore du Limousin. 201 records from (Table 1) Benthic foraminiferal genera in DSDP Core 95-612-69. 882456 records from South Australia Fauna Observations. 15956 records from Algae (S). 1652 records from Depletion Fishing in the river "Grote Nete" and "Kleine Nete" 1989-1996. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 5106 records from (Table 2) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-844B. 51 records from Packer Collection / Xenochilicola bees, Chile. 1626 records from Ornithologie ZMK. 382 records from Reptilia ZMK. 107 records from (Appendix 3) Calcareous nannofossils in ODP Hole 113-690B. 10255 records from Araneae Collection. 18 records from Survey of the native freshwater opossum shrimp (Mysis relicta) in Ireland. 423 records from (Table 2) Benthic foraminiferal distribution at ODP Hole 127-795B. 140 records from (Table 3) Counts of dead (not stained) benthic foraminifera from stations in the northern Gulf of California. 16452 records from Fungus herbarium, UiB. 2506 records from Museu Paraense Emilio Goeldi - Opiliones Collection. 3 records from A new killifish genus and species from the coastal plains of northeastern Brazil (Teleostei: Cyprinodontiformes: Rivulidae).. 2876 records from Naturalis National Natural History Museum (NL) – Mollusca fossils. 111682 records from British Phycological Society - Seaweed data for Great Britain and Ireland. 2920 records from HSU Wildlife Mammals. 146809 records from OHN. 52 records from The high alpine bee fauna (Hymenoptera: Apoidea) of the Zillertal Alps, Austria. 30 records from Specimens from India at the University Museum at the University of Bergen. 192273 records from Field Museum of Natural History (Zoology) Mammal Collection. 695 records from (Table 5) Benthic foraminiferal community at DSDP Site 94-610. 3 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas I. Zwei neue Arten der Gattung Suctobelba Paoli aus der Oberlausitz (DDR): Suctobelba scalpellata n. sp. und Suctobelba secta n. sp.. 496 records from (Table 4) Benthic foraminifera in Northwest Indian Ocean surface sediments. 2913345 records from Especímenes INBio. 303 records from Ichthyologie ZMK. 90 records from (Table 2) Occurrence of larger benthic foraminifers in ODP Hole 133-823C. 1489 records from (Figure 4) Dinoflagellate cyst measured on sediment core AI07-03G. 6 records from Echinodermata ZMK. 108 records from (Table 7) Planktonic foraminifera species in bottom sediments of Core ML5_348, North Atlantic. 1 records from Oribates angulatus. 158552 records from Lund Museum of Zoology (MZLU). 5605 records from Distribution of barnacles, bivalves, gastropods, and calcified worm tubes in sediment samples collected between 1995 and 2010 in the San Francisco Bay coastal system. 439 records from Museu Paraense Emilio Goeldi - Scorpiones Collection. 2 records from Amphibia ZMK. 5 records from Erethistoides sicula, a new catfish (Teleostei: Erethistidae) from India.. 1 records from Ctenophora ZMK. 1 records from Nothrus bicarinatus. 154 records from Specimens from India at the NTNU University Museum in Trondheim. 1725 records from (Table 1) Planktonic foraminifer stratigraphy in ODP Hole 167-1021C sediments. 1 records from Protozoa ZMK. 12876 records from Zoological Museum Amsterdam, University of Amsterdam (NL) – Mollusca_Pectinoidea. 24 records from 10) SST, IRD and benthic foraminiferal d18O data from the Norwegian Sea core MD95-2010: revised chronology for the Last Interglacial (period 134-110 ka). 1 records from Nothrus bispinosus. 2 records from Vermes ZMK. 1 records from Oribates badius. 3221 records from Road Kill Survey. 496203 records from Bees, Wasps and Ants Recording Society - Bees, Wasps and Ants Recording Society - Trial Dataset. 39 records from Arachnologie ZMK. 6 records from Mammalia (JNHM-MM). 38 records from (Table T2) Dinoflagellate cysts and pollen/spore yield and preservation in ODP Site 188-1166. 223522 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Butterfly data up to current day. 15046 records from Colección de mariposas del Museo de Entomología de la Universidad del Valle. 220 records from (Figure 1b) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3182. 576881 records from RB - Rio de Janeiro Botanical Garden Herbarium Collection. 195 records from (Table T3) Planktic foraminiferal assemblages in sediments of ODP Hole 198-1210A, Shatsky Rise, Pacific Ocean. 3182 records from (Table 15B) Occurrences of planktonic foraminifers in DSDP Hole 90-593, samples 593-31-CC through 593-60-CC. 3387 records from Visherintroductie - Reintroduction of the fishes chub, dace, burbot, and brown trout in Flanders, Belgium. 448 records from (Appendix A) Abundance of ostracode species from DSDP Hole 48-401. 1 records from Bryozoa ZMK. 26 records from Schwedische Oribatei (Acari). III.. 450 records from Sea surface temperature and salinity reconstructions for sediment core LaPAS-KF02. 20991 records from Field Museum of Natural History (Zoology) Bird Egg Collection. 5199 records from FCAB - Herbário Friburguense. 103 records from Mammalogie ZMK. 19 records from Inventaire National du Patrimoine Naturel : Données sur Tamias sibiricus (Ecureuil de Corée). 171 records from (Table T1) Occurrence of Lower Cretaceous planktonic foraminifera in ODP Hole 171B-1049A. 2 records from Pantopoda SMF. 456 records from (Table 1) Mollusc biostratigraphy of a sediment core obtained near Gross Pampau. 6622 records from The Fossil Fish Collection at the Jura-Museum Eichstätt. 111 records from Microplankton abundance measured on water bottle samples during AEGAEO cruise LIA-8. 27 records from Hybridization in Umbridae in the Hudson River, New York, with Designation of Neotypes for Umbra limi and Umbra pygmaea.. 10840 records from Bird skin collection, Natural History Museum, University of Oslo. 1532 records from John Muir Trust - Plants, Bryophytes and Lichens recorded on the Skye Estate during October 1995 â October 2004.. 1 records from Hesperinus ninae Papp & Krivosheina (Diptera: Hesperinidae) from Georgia: the second record of this peculiar species. 1243 records from Crustacea ZMK. 27290 records from Bird Monitoring Data. 1 records from Tunicata ZMK. 17 records from Malakologie ZMK. 2 records from Cnidaria ZMK. 155255 records from CAS Invertebrate Zoology (IZ). 16621 records from Crustacea collection of National Museum of Nature and Science. 32109 records from Herbier de Nouvelle-Calédonie. 1 records from Description of a new species of Echiodon (Teleostei: Carapidae) from the South Atlantic Ocean.. 400 records from Colección Hidrobiológica del Chocó. 1 records from Porifera ZMK. 3061 records from (Table 4) Distribution of Miocene planktonic foraminifers in sediments of ODP Hole 138-846B. 15925 records from Merseyside BioBank - North Merseyside Other Taxa (verified). 1 records from On centipedes (Chilopoda) of Albania, 2. 1933 records from Gloucestershire Environmental Data Unit - Gloucestershire BAP Priority Species - Dormouse. 396 records from (Appendix) Bathyal benthic foraminifera in ODP Hole 166-1006A sediments. 1 records from On the Chilopoda from Turkey. 111 records from (Table T5) Relative abundance of Eocene plant microfossil taxa of ODP Site 188-1166. 3268 records from (Table 1) Distribution of early Eocene to early middle Eocene benthic foraminifera in DSDP Hole 93-605. 61 records from Shrews of Poland. 4 records from New country records of reptiles from Laos. 1 records from (List 1) Summary of fossil Mollusca found in Schleswig-Holstein, Germany. 44 records from (Data S1) Palynology of IODP Hole 318-U1360A. 3762 records from Inventaire National du Patrimoine Naturel : Flore protégée du Dauphiné. 16696 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Fungi and Lichen Observation Records. Pre-2010 for Cumbria.. 513 records from Hemiptera (Heteroptera) collection of National Museum of Nature and Science. 1029 records from Freshwater plants of Cameroon. 396314 records from British Lichen Society - BLS Lichen Database: English churchyards. 513 records from Occurrences des observations de la campagne REMMOA Antilles (2008). 217 records from Succession of benthic hard-bottom communities abundance at station Errina2012_MDD7. 19 records from The first case of aggressive mimicry among lamprologines in a new species of Lepidiolamprologus (Perciformes: Cichlidae) from Lake Tanganyika.. 14420 records from Colección Nacional de Foraminíferos - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 102 records from John Muir Trust - A Lichen Survey of the Ben Nevis Plateau. 89 records from Collection Crustacea - PUM. 259 records from (Table 2) Abundances of planktonic and benthic foraminifera in ODP Hole 130-807A. 229 records from Zur Faunistik und Ökologie der Caribiden (Caribidae, Coleoptera) ausgewählter Trockenstandorte in der 'Nuthe-Nieplitz-Niederung' (Land Brandenburg). 83679 records from Scottish Wildlife Trust - Commissioned surveys and staff surveys and reports for SWT reserves. . 9 records from A new species of Metahomaloptera (Teleostei: Balitoridae) from China.. 2 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2010. 200 records from Zoological collection of the National Museum. 803 records from (Table 7) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1020B sediments. 335 records from Meiofaunal abundance in sediments obtained during RRS Discovery cruise D297. 631 records from UCM Bird Eggs/Nests Collection (Arctos). 11251 records from Herbarium areqvipense (HUSA). 1641 records from NCSM PaleoBotany Collection. 67 records from Hertfordshire Biological Records Centre - Roadside Verge Survey 1986 (Herts data from Cambs WT survey). 50 records from (Table T3) Biogenic and mineral composition of sediments cored in Hamburg-Wulksfelde. 1 records from A new myrmicine ant genus from Malaysia with uncertain affinities (Hymenoptera: Formicidae).. 453 records from Colección de Fauna Marina del Centro Oceanográfico de Málaga (I.E.O.): CFM_IEOMA. 2080 records from The Fossil Fish Collection at the Bayerische Staatssammlung für Paläontologie und Geologie. 2223 records from Colección de Zoología Invertebrados - Otros invertebrados. 9 records from Chenopodium vulvaria. 308 records from Record of 7 acritarch taxa, Mg/Ca sea-surface temperatures and palynological preparation data from the Miocene, Pliocene and Pleistocene of IODP Site 303-U1308. 1127 records from Census of the secondary forests of the Lama forest reserve (Southern Benin). 1329 records from Colección de Invertebrados Cenpat (CNP-INV). 385 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Laridae. 1 records from Identification of the species of Gnamptogenys Roger in the Americas.. 1 records from Chilopoden und Diplopoden aus Jugoslavischen Höhlen. 19700 records from RAVON (NL) - Fish observations extracted from historic reports 1860-1907. 21091 records from NCSM Birds Collection. 1000 records from Colección Limnológica del Chocó. 749213 records from Historical Bird Atlas. 1376 records from Vertical distribution of nannofossils in the section of DSDP Site 72-516. 1614 records from Culture Collection of Algae. 28370 records from UAM Bird Collection (Arctos). 151 records from (Table T1) Biostratigraphy and distribution of Quaternary and Miocene calcareous nannofossils in ODP Site 188-1165. 9 records from Corumbataia britskii (Siluriformes: Loricariidae: Hypoptopomatinae) a new species from the upper Rio Parana basin, Mato Grosso do Sul, Central Brazil.. 2234 records from (Figure 1) Dinoflagellate cyst stratigraphy of DSDP Hole 80-548A. 155 records from Bammentaler Duft- und Heilkräutergarten. 564 records from Streamlining the use of BOLD specimen data to record species distributions: a case study with ten Nearctic species of Microgastrinae (Hymenoptera: Braconidae). 30 records from Guadeloupe_Taro. 8326 records from Derbyshire Biological Records Centre - Derbyshire Invasive Vascular Plants (INNS) 1900 - 2011. 1091 records from (Table 5) Distribution of benthic foraminifers from ODP Site 134-832. 4601 records from (Table 2) Distribution and relative abundance of mid-Cretaceous planktonic foraminifers at DSDP Site 79-547A. 16568 records from Inventaire National du Patrimoine Naturel : Données des campagnes de Suivi Aérien de la Mégafaune Marine (SAMM) de France métropolitaine. 432 records from Royal Horticultural Society - RHS Hemerocallis gall midge (Contarinia quinquenotata) monitoring. 30926 records from Annelida collection of National Museum of Nature and Science. 15 records from (Table 15) Calcareous nannofossil occurrences in ODP Hole 130-805C. 688 records from Algae, Norwegian College of Fishery Science. 1992 records from (Table 8) Benthic foraminifera in Pliocene sediments of DSDP Hole 90-590A. 645788 records from Norwegian Biodiversity Information Centre - Other datasets. 2856 records from (Table S3) Significant benthic foraminifera species in ODP Hole 164-997A. 8 records from (Table 1) Distribution of benthic foraminifera in GIK_Plankton-B sample. 21694 records from arim. 6 records from Monomorium dentatum sp. n., a new ant species from Egypt (Hymenoptera: Formicidae) related to the fossulatum group.. 1415 records from Plant observations from Białowieża National Park. 1 records from Oribates orbicularis. 94 records from John Muir Trust - Vascular Plants and Bryophytes of Glen Sligachan. 270 records from Meiofaunal abundance in sediments obtained during RRS Charles Darwin cruise CD179. 337 records from One century of vegetation change on Isla Persa, a nunatak in the Bernina massif in the Swiss Alps. 8 records from Torpedo formosa sp. nov., a new species of electric ray (Chondrichthyes: Torpediniformes: Torpedinidae) from Taiwan.. 7 records from (Table 4) New palynological record of sediments from Odderade. 136 records from Grillhütte Wettsaasen, Wiese, Hecken. 3422 records from The Scottish Ornithologists' Club - Highland Breeding Bird Data 2002-2003 - non-sensitive breeding species. 1658 records from Aves Argentinas / Asociación Ornitológica del Plata - Conteo anual de chorlos de pastizal en Argentina - Campaña enero 2009. 29532 records from MPM Herpetology. 7 records from A new species of the genus Bothriomyrmex Emery, 1869 (Hymenoptera: Formicidae: Dolichoderinae) from Costa Rica.. 8714 records from Greater Manchester Ecology Unit - Bird Records held by Greater Manchester Ecology Unit. 23 records from Description of Cathorops manglarensis, a new species from the Colombian Pacific, with redescription of Cathorops multiradiatus (Siluriformes; Ariidae).. 553 records from Composición florística y estructura de una parcela permanente en bosques humedos tropicales del resguardo Emberá Chontadural, municipio de Mutatá, Antioquia. 21 records from Meiofauna densities from in situ feeding experiments in the Nazare Canyon conducted with sediments from ROV push-core JC10-95-PUC02. 19 records from (Table S1) Calcareous nannoplankton morphometric analyses performed of Cismon sediment core samples. 378 records from Greater Manchester Ecology Unit - Distribution of Badgers in Greater Manchester. 210 records from (Table 2) Neogloboquadrina plexus coiling direction at DSDP Site 49-410 and Holes 81-552A, 94-610E, and 94-611C. 34 records from Caddisfly Records, Edenvale, Co. Wexford 2010. 1 records from Arthropoden aus südostalpinen Höhlen.. 9056 records from Tunicates collection (IT) of the Muséum national d'Histoire naturelle (MNHN - Paris). 13503 records from Collection of various insect orders, Natural History Museum, University of Oslo. 33 records from (Table 6) Distribution and abundance of calcareous-nannoplankton species in the Cretaceous sediments of DSDP Hole 62-466. 1288 records from (Table 4) Distribution of benthic foraminifers from ODP Hole 134-829A. 29087 records from Naturalis Biodiversity Center (NL) - Collembola. 2493 records from (Table T1) Foraminifer abundance of ODP Hole 188-1165B. 58 records from A revision the Australian species of the ant genus Myrmecina (Hymenoptera: Formicidae).. 1 records from Die Chilopodenfauna Griechenlands. 2 records from On the centipedes (Chilopoda) of the Republic of Macedonia. 724 records from University of Amsterdam (NL) - Páramo vegetation research, Talamanca Cordillera, Costa Rica. 8 records from (Table 1) Maximal abundance of dominating species and phytoplankton groups within the Gelendzhik polygon in 2002-2005. 9 records from A new species of Margaromantis Piza, 1982 ( Insecta : Mantodea ) from Brazil. 7000 records from CCBER Ornithology Collection. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 3 records from Miriapodi cavernicoli del Marocco, della Sardegna e del Piemonte. 1602 records from (Table T3) Abundance of dinoflagellates and other palynomorphs in Maastrichtian-Eocene sediments from ODP Hole 189-1172D. 6812 records from Invertebrate collection of University of Oulu Zoological Museum. 3045 records from ESAS cetacean sightings from 1980 to 2003.. 9 records from A new species of Margaromantis Piza, 1982 (Insecta: Mantodea) from Brazil. 285 records from Sylva Foundation - European Pear Rust (Gymnosporangium sabinae) monitoring. 1993964 records from Museum of Comparative Zoology, Harvard University. 5 records from New records of Paraleptophlebia werneri Ulmer, 1920 and P. strandii (Eaton, 1901) from Finland (Ephemeroptera, Leptophlebiidae). 3117 records from Naturalis National Natural History Museum (NL) – Coelenterata. 2 records from Pollen analysis of sediment profile MU01 from Muggesfelder See. 1119094 records from Fundación Biodiversidad, Real Jardín Botánico (CSIC): Anthos. Sistema de Información de las plantas de España. 9948 records from Bees of Canada / Gschwendtner property collection. 91 records from Foraminifera assemblage in surface sediments of the Skagerrak/Kattegat area. 12 records from (Appendix B) Stratigraphic occurrence of radiolarian special and species groups in sediments of ODP Hole 199-1218A. 54233 records from Naturalis Biodiversity Center (NL) - Mammalia. 3313 records from Dorset Environmental Records Centre - Bryophyte Survey of the Poole Basin Mires - NBN South West Pilot Project Case Studies. 21541 records from Herbarium of the Université Libre de Bruxelles. 6821 records from Staatliches Naturhistorisches Museum Braunschweig - Coleoptera Collection. 60 records from The genera of the Neotropical armored catfish subfamily Loricariinae (Siluriformes: Loricariidae): a practical key and synopsis.. 5043 records from RSPB - Dartford Warbler national surveys in the UK (SCARABBS). 5155977 records from Australia's Virtual Herbarium. 1547 records from West Wales Biodiversity Information Centre - Sea Trust Stena Europe Survey of Cetaceans in the St Georgeâs Channel, April 2004- April 2011. 450 records from John Muir Trust - Species Records for John Muir Trust Properties 2007-2009. 21 records from LBV-Kindergruppen Markt Tussenhausen. 2625 records from (Table 1) Stratigraphic distribution of planktonic foraminifera from the uppermost Miocene to upper Pliocene in ODP Hole 134-832B. 299586 records from SEAPOP NINA. 35685 records from VIES - Herbário Central da Universidade Federal do Espírito Santo. 38841 records from Herbier de Strasbourg. 1695 records from Field Study Group of the Dutch Mammal Society (NL) - 2005 - Mammal Survey Pol'ana Biosphere reserve, Slovakia. 120208 records from Inventaire National du Patrimoine Naturel : Poissons d'eau douce de France. 28 records from Colección de Cocodrilos y Caimanes Museo de La Salle Bogotá (MLS). 31 records from RSPB - Spotted crake national survey in the UK in 1999 (SCARABBS). 7551636 records from Birds Australia, Birdata. 48 records from Tardigrada collection of National Museum of Nature and Science. 8 records from (Table 1) Major and minor element concentrations in the livers of polar bears (Ursus maritimus) from Canada, Alaska and Greenland. 16 records from Moenkhausia pankilopteryx, new species from rio Tocantins drainage, Brazil (Ostariophysi: Characiformes, Characidae).. 60163 records from Rapid Assessment Program (RAP) Biodiversity Survey Database. 6211 records from NMMNH Mammal. 23 records from Wattuntersuchung (Cuxhaven). 555 records from (Appendix 1) Abundances of benthic forminifera in ODP Hole 113-689B. 1 records from Flora of Suriname, volume VI, part I. 1150 records from RSPB - Great Yellow Bumblebee sightings data in the UK, 1990 onwards (RSPB, BBCT, HBRG).. 637 records from Dinoflagellate cysts in western equatorial Atlantic surface sediments. 46 records from (Table T2) Stratigraphic distribution of dinoflagellates and pollen/spores by age class, ODP Leg 188 sites. 12509 records from The Bat Conservation Trust - Hibernation Survey. 1 records from Nothrus palliatus. 2 records from Ein Beitrag zur Landtierwelt von Korfu. Chilopoda. 15 records from Chenopodium. 1109 records from Gloucestershire Centre for Environmental Records - Gloucestershire BAP Priority Species - Water voles. 157292 records from Hertfordshire Natural History Society Flora Group - Hertfordshire Flora Survey Records 1987-2005. 200913 records from University of British Columbia Herbarium (UBC) - Bryophytes Collection. 39 records from Colección de Urocordados. 194165 records from Vascular Plant Herbarium, UiB. 3319 records from Gloucestershire Centre for Environmental Records - Gloucestershire Amphibians not including great crested newts. 55 records from Colección de Platyhelminthes del Museo Nacional de Historia Natural de Chile. 56302 records from Kathryn Kalmbach Herbarium. 320 records from (Figure 1a) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3180. 92 records from Type specimens of invertebrate collection at University of Oulu Zoological Museum. 163 records from Entomofauna laguna El Tinije. 97672 records from CAS Ornithology (ORN). 607 records from Líquens d'Andorra. 1 records from Zetes morticinus. 17 records from Meiofauna abundances in sediments from the Storegga Slide (Norwegian Sea) obtained during the VICKING expedition in 2006. 493 records from Phytoplankton long-term time-series at the fixed coastal station in the Gulf of Naples, data for the years 1984-1991. Part 3. 4852611 records from Bird Ringing Centre in Sweden (NRM). 153532169 records from EOD - eBird Observation Dataset. 98 records from Colección Nacional de Heliconias. 1 records from Graureiher in Lans. 88693 records from Ichthyology Collection - Royal Ontario Museum. 2087 records from Banco de Germoplasma del Jardín Botánico Atlántico. 4873 records from Berkshire Reptile and Amphibian Group - BRAG - Berkshire Reptile and Amphibian Records. 6004 records from Colección Limnológica Universidad de Antioquia. 42 records from (Fig. 4) Relative proportions of the most abundant chironomid taxa in the Lake Temje sediment core. 262 records from (Appendix G) Benthic foraminifera extinction group species in ODP Hole 167-1012B. 7 records from Pseudochromis lugubris and P. tonozukai, two new dottyback fish species from the Indo-Australian Archipelago (Perciformes: Pseudochromidae: Pseudochrominae).. 22167 records from Natural History Museum Maastricht (NL) - Herbarium. 1911651 records from Consortium of California Herbaria. 798 records from Biological Records Centre - Irish Otter Dataset. 8026 records from Primera caracterización biológica de aves del proyecto "Incorporación de la Biodiversidad en el sector cafetero en Colombia". 976 records from (Table 2) Benthic foraminifera in Pliocene sediments of DSDP Hole 89-586B. 18900 records from UCBG TAPIR Provider. 3015 records from Aquatic Oligochaeta of Ireland. 876 records from (Supplement 1) Most common taxa or groups of coccoliths from ODP Site 1233 (past dataset) covering the last 70 kyr. 1275 records from (Appendix B) Dinoflagellate cysts eco-groups of DSDP Hole 38-338. 40481 records from Biological Records Centre - Soldier Beetle and Jewel Beetle (Coleoptera; Cantharoidea and Buprestoidea) records for Britain and Ireland to 2000. 34 records from National System of Protected Areas in Poland - Fungi. 3 records from New species of myrmicine ants from Western Australia (Hymenoptera: Formicidae).. 37558 records from Tasmanian Museum and Art Gallery provider for OZCAM. 1 records from Scutellista caerulea (Fonscolombe, 1832) (Hymenoptera: Pteromalidae), new to New Zealand for the second time!. 34 records from New records in vascular plants alien to Kyrgyzstan. 2000 records from Herbario virtual bosques secos de Colombia - Sección herbario TOLI (UT). 1245 records from Nematode abundance in sediments obtained during the Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 3381 records from (Table 10B) Occurrences of planktonic foraminifers in selected samples of DSDP Hole 90-588A. 1200 records from (Table 5) Relative abundances of stratigraphically useful planktonic foraminifers from ODP Hole 167-1014A sediments. 12 records from Dispatch from the field: ecology of ground-web-building spiders with description of a new species (Araneae, Symphytognathidae). 589 records from (Appendix B) Benthic foraminifera extinction group polpulation of ODP Hole 184-1146A. 70111 records from Kyushu University Museum Coleoptera Collection. 49637 records from Monitoring data from the federal state Hesse (Germany). 149 records from (Appendix C) Benthic foraminiferal census data for extinction, uniserial survivor and high-flux, low-oxygen tolerant groups for ODP Hole 160-967A. 666165 records from iNaturalist research-grade observations. 807 records from Reunion_Coffea. 477 records from (Table 2) Distribution of foraminifera in the Miocene section of ODP Hole 133-816A. 2473 records from (Table 1) Distribution of planktonic foraminifers at DSDP Hole 90-590A. 175 records from (Table T3) Calcareous nannofossil stratigraphy of ODP Hole 198-1207B. 4399 records from Fundacin Miguel Lillo - Coleccin Entomolgica. 36459 records from Colección Nacional de Mastozoología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 73 records from A new handfish, Brachionichthys australis sp. nov. (Lophiiformes: Brachionichthyidae), with a redescription of the critically endangered spotted handfish, B. hirsutus (Lacepede).. 5913 records from An Atlas of Breeding Birds of the Burren and Aran Islands 1993 - 1996. 43298 records from Countryside Council for Wales - Pembrokeshire Marine Species Atlas. 4 records from A new ant genus from the southwestern United States.. 314 records from Invertebrate collection of the Seto Marine Biological Laboratory, Kyoto University. 8518 records from Upper Silesian Museum, Bird Observations. 38 records from Inventario de Murciélagos Buena Vista, Jaramá, Yopal, Casanare. 13 records from (Table 2b) Species of planktonic foraminifera found in surface layer bottom sediment at Station Vy20-3217GR. 29691 records from University of Amsterdam (NL) – Benthos monitoring of the North Sea research database. 2 records from Neue Milbenarten aus Kärnten. 14760 records from Outer Hebrides Biological Recording Project - OHBRP Insects Dataset - Outer Hebrides. 323085 records from North & East Yorkshire Ecological Data Centre - North and East Yorkshire Ecological Data Centre - Non-sensitive Records from all taxonomic groups.. 2391 records from Ohio State University Tetrapod Division - Reptile Collection (OSUM). 162886 records from CONN. 1077 records from BioGIS - Fish - HUJ collections. 752 records from Arthropoda Collection of the Seto Marine Biological Laboratory, Kyoto University. 1390 records from Caracterización de avifauna de la subcuenca del Río San Pedro, San Pedro, Valle del Cauca. 1369 records from Chromista Collection of the Seto Marine Biological Laboratory, Kyoto University. 2115 records from Algae specimenｓ database of Shizuoka Prefecture Museum of Natural History. 1594 records from Musée Vert ornithology collection. 80 records from Landschaftsschutzgebiet Schmutterwald. 3002 records from Colección de Peces Universidad Católica de Oriente. 2923 records from Caracterización de flora, edafofauna epígea, anfibios y aves del complejo de Páramos de Sotará, Cauca. 9787 records from Finnish Entomological Database: Hymenoptera. 8629 records from National Taiwan University. 1 records from Hypochthonius rufulus. 1 records from Oribates ovatus. 304689 records from Aranzadi Ringing Scheme (bird ring-recovery data). 77 records from Terrestrial gastropods of Srebarna Nature Reserve, North-Eastern Bulgaria (Gastropoda). 3546 records from Dorset Environmental Records Centre - Dorset SW Pilot species dataset. 94 records from (Fig. 3) Inter-core correlation of Ca/Fe ratios and magnetic susceptibility supported by IRD and N. pachyderma (sin) of sediment core GeoB11035-1. 1 records from Hoplophora crinita. 21752 records from HUCS - Herbário da Universidade de Caxias do Sul. 38975 records from H.A. Stephens Herbarium. 13968 records from NYSM Birds. 1896 records from Cnidaria Collection of the Seto Marine Biological Laboratory, Kyoto University. 2330 records from Seaweed (Plantae) Collection of the Seto Marine Biological Laboratory, Kyoto University. 22 records from Bacteria Collection of the Seto Marine Biological Laboratory, Kyoto University. 104520 records from Recent Invertebrates Specimens. 1733 records from Birds collection of Abiko City Museum of Birds. 2043 records from Mollusca Collection of Natural History Museum and Institute, Chiba. 30000 records from Birds collection of Yamashina Institute for Ornithology. 1000 records from Mollusca Specimens of Oiso Municipal Museum. 58 records from Schulgelände Kranich-Gymnasium (Salzgitter). 915 records from Colección de Coleoptera (Tenebrionidae) del sureste de la Península Ibérica de la Universidad de Granada. 1 records from (Table T4) Calcareous nannofossil stratigraphy of ODP Hole 198-1208A. 17252 records from BioGIS - Vascular plants - HUJ Herbarium. 9 records from Vigna yadavii (Leguminosae: Papilionoideae), a new species from Western Ghats, India. 418 records from Type Collection of the Seto Marine Biological Laboratory, Kyoto University. 151 records from UCM Vertebrate Observations Collection (Arctos). 10046 records from Biological Records Centre - Crayfish (Crustacea; Astacura) data for Britain and Ireland to 2003. 179 records from (Table 4) Distribution of Upper Cretaceous agglutinated benthic foraminifers in ODP Hole 129-801A. 89 records from Devon Biodiversity Records Centre - Devon Himalayan balsam data 1997 to 2007. 14172 records from Biological Resource Center, Department of Biotechnology, National Institute of Technology and Evaluation. 22 records from A synoptic review of the ants of California (Hymenoptera: Formicidae).. 106 records from Phylogeny of Corynoptera Winnertz and related genera, with the description of Claustropyga gen. nov. (Diptera, Sciaridae). 10866 records from Heteroptera of Ireland. 202 records from (Appendix A) Relative abundance of benthic foraminifera in ODP Hole 138-844C. 102 records from (Table 1) Planktonic foraminifera counts and stable oxygen isotope ratios of Pacific Ocean surface sediments. 16 records from Mollusca Colelction of the Seto Marine Biological Laboratory, Kyoto University. 169 records from HTSAw - Xiloteca do Trópico Semiárido. 23046 records from Hemipteran specimens of Iwate Prefectural Museum. 391 records from An updated checklist of aquatic plants of Myanmar and Thailand. 2 records from Discothyrea sringerensis (Hymenoptera: Formicidae) a new ant species from India.. 115 records from RSPB - Bringing Reedbeds to Life Amphibian Survey of two key reedbed sites in England in 2010.. 63961 records from observe_tuna_bycatch_ecoscope. 209 records from (Table 2) Ostracoda community from DSDP Hole 95-613. 1808 records from Fongs d'Andorra. 4 records from Note on some antlions from Mozambique (Neuroptera: Myrmeleontidae). 1275 records from (Table T6) Planktonic foraminifera stratigraphy of ODP Hole 198-1209, Zones P12-P18. 71 records from Phytoplankton abundance in the wadden sea off List, Sylt, North Sea in 2007. 39 records from Kryptopterus geminus, a new species of silurid catfish (Teleostei: Siluridae) from mainland Southeast Asia.. 69 records from Revision of the subgenus Aulacomyrma Emery of the genus Polyrhachis F. Smith, with descriptions of new species.. 4067 records from Coleção de Polychaeta do Museu Nacional. 26 records from Nanochromis sabinae, a new cichlid species (Teleostei, Cichlidae) from the Upper Congo River area and Northeast Gabon.. 9399 records from Merseyside BioBank - Merseyside BioBank Active Naturalists (unverified). 592 records from Spiders_of_French_Guiana. 324 records from People's Trust for Endangered Species - Noble Chafer: Post-BAP records from 1998 onwards. 164 records from Taxonomy of the catfish genus Pseudoplatystoma Bleeker (Siluriformes: Pimelodidae) with recognition of eight species.. 7 records from A new species of Trichomycterus (Siluriformes: Trichomycteridae) from south Brazil and redescription of T. iheringi (Eigenmann).. 4498 records from Flora of Japan Specimen Database. 4230 records from Derbyshire Wildlife Trust - Derbyshire Wildlife Trust Coleoptera Records up to Dec 2012. 182 records from Faunistic Diversity of Spiders (Araneae) in Galichitsa Mountain (FYR Macedonia). 57928 records from Zoological Museum Amsterdam, University of Amsterdam (NL) - Lepidoptera_Nymphalidae_Palearctic. 21749 records from University of Lethbridge Herbarium (LEA). 637 records from Fossil occurrence from planktonic foraminiferas from IODP Hole 315-C0002B. 2708 records from (Table T1) Benthic foraminfera stratigraphy of ODP Hole 199-1218A and 199-1219A sediments. 23 records from First record of the genus Venanus (Hymenoptera: Braconidae: Microgastrinae) in Mesoamerica, with the description of two new species from Costa Rica. 2275 records from UFRN-Fungos - Herbário UFRN - Fungos. 3065 records from Colección de Ofidios Museo de La Salle Bogotá (MLS). 11 records from A new rainbowfish (Teleostei: Melanotaenioidei: Bedotiidae) from the southeastern highlands of Madagascar, with comments on the biogeography of Bedotia.. 66035 records from Bedfordshire and Luton Biodiversity Recording and Monitoring Centre - Bedfordshire Micro Moths (BNHS) - 1820-2009. 6884 records from Herbario CDMB - Jardín Botánico Eloy Valenzuela. 242 records from (Supplement 3) Dinoflagellate cyst concentrations of the three transects OMZ (GeoB 12312, 12321, 12331), below-OMZ-seep (GeoB 12326), and OMZ-seep (GeoB 12328). 252 records from (Table T11) Calcareous nannofossil stratigraphy of ODP Hole 198-1212B. 21188 records from National Bat Database of Ireland. 40 records from Phytoplankton abundance and species composition in the Gulf of Naples in June 1999 at station MCSSII-phyto102-110. 473 records from (Table 1) Foraminifera abundance of ODP Hole 162-985A sediments. 6774 records from Colección Nacional de Paleopalinología - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 86 records from Appendix A: Results of the pollen analysis of the PG1755 core from Lake Billyakh. 164 records from EcoRecord - Flatworm Records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 2754 records from (Table 7) Benthic foraminifera in middle-late Miocene sediments of DSDP Site 90-590. 3 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Cinclidae. 246 records from CaCO3, biogenic opal, TOC, and microfossil observations of sediment core MR06-04_PC23A. 4745 records from Herbier A. Le Grand (BOUM). 16 records from Beiträge zur Kenntnis der Oribatiden (Acari) Europas III. Suctobelbella alloenasuta n. sp. und Suctobelbella messneri n. sp. sowie die bisher aus der DDR bekannten Arten der nasalis-subtrigona-Gruppe (Suctobelbidae). 205653 records from Inventaire National du Patrimoine Naturel : Oiseaux nicheurs de France. 617 records from Meiofauna abundance of westerm Mediterranean Sea seep sediments. 1 records from Murcia trimaculata. 54 records from Three new species of Gastromyzon (Teleostei: Balitoridae) from southern Sarawak.. 3 records from Description of male Tylorida sataraensis Kulkarni, 2014 (Araneae, Tetragnathidae) with notes on habits and conservation status . 11 records from Pollen profile from sediment core AV14_K2-1. 1035 records from National Museum Of Marine Science & Technology. 55 records from Towards the conservation of parasitoid wasp species in Canada: Preliminary assessment of Microgastrinae (Hymenoptera: Braconidae). 33 records from Phytoplankton abundance and species composition in the Gulf of Naples in March 1999 at Station MCSSI-phyto57-65. 1752 records from Herbier National de Mauritanie (HNM). 1 records from (Table 1) Concentration of PCB and other contaminants in blood plasma of polar bears (Ursus maritimus) from Svalbard. 238 records from John Muir Trust - List of Lichen Species recorded on high ground in the Ben Nevis range. 5 records from A new cleaner goby of the genus Elacatinus (Teleostei: Gobiidae), from Trindade Island, off Brazil.. 31273 records from SABCA. 5152 records from (Table T1) Plankontic foraminifera stratigraphy of ODP Site 184-1143. 10 records from A new species of Orthosiphon (Lamiaceae) from Angola. 10329 records from KUBI Ichthyology Tissue Collection. 1900 records from Fungi Collection. 33173 records from Global Lacustrine Diatoms. 353326 records from UCJEPS TAPIR Provider. 713 records from (Figure 6) Total organic carbon content and counted dinoflagellate cysts of sediment core GeoB10706-3. 424 records from Field Study Group of the Dutch Mammal Society (NL) - 2011 - Mammal Survey Biokovo Nature Park, Croatia. 5 records from Notes on the biology, distribution, biosecurity status and history in New Zealand of Macrotrachelia nigronitens (Stål, 1860) (Heteroptera: Anthocoridae). 2966 records from Bolivian Amazon lowland fish metacommunity data. 1 records from A new Camponotus from Madagascar and a small collection of ants from Mauritius.. 850 records from Shellfish (NHMK-MS). 1914 records from Macrophytes_CLF. 15927 records from Derbyshire (Derby Museum) Biological Records Centre - Derbyshire & Peak District Protected Species Database (Summary of available records 1970- 2008). 181 records from Alien Species in Poland - Animals. 85 records from Countryside Council for Wales - Welsh Lesser Horseshoe Bat Summer Roost Surveillance Database. 366 records from (Appendix A) Abundance of selected coccolithophores in sediment core DS97-2P, North Atlantic. 2 records from Male sleeping aggregation of multiple Eucerini bee genera (Hymenoptera: Apidae) in Chapada Diamantina, Bahia, Brazil. 11 records from Six new species of the spider family Ochyroceratidae Fage 1912 (Arachnida: Araneae) from Southeast Asia. 178 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Records of Fossil Molluscs for Great Britain. 7 records from An unusual new species of Micraspis Chevrolat (Coleoptera: Coccinellidae) from northeastern India. 3 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 693 records from (Figure 2e) Distribution of planktonic foraminifera in bottom sediments of Core Vy20-3205. 64 records from (Table 4) Pleistocene nannofossil range chart for ODP Hole 134-827B. 387106 records from University of California Museum of Paleontology. 6 records from Description of two new species of the catfish genus Trichomycterus from southeastern Brazil (Siluriformes: Trichomycteridae).. 7 records from Kryptolebias sepia n. sp. (Actinopterygii: Cyprinodontiformes: Rivulidae), a new killifish from the Tapanahony River drainage in southeast Surinam.. 7 records from (Table 5) Concentrations of organochlorine pesticides in adipose tissue of polar bears (Ursus maritimus) between 1991-2007. 537 records from The French National Collection of forage and turf species (grasses and legumes).. 40697 records from Mammals housed at MHNG, Geneva. 1 records from Damaeus bicostatus. 100 records from BIRDRACE Lohmanns Öömi-Studenten. 3 records from A new species of Lygistorrhina Skuse (Diptera: Sciaroidea: Lygistorrhinidae) from South Africa. 4268 records from Free-living marine Nematodes from Ali, Rada Tilly and El Limite sandy beaches (Chubut, Argentina) 2006.. 8706 records from NINA botanical collection. 24 records from (Tables 1,2) Site characteristics and phenotypic attributes of King Penguins (Aptenodytes patagonicus) on Possession Island. 1 records from Asya hayvanlari ve zoogeografiyasi hakkinda. Asiatische Beiträge. VIII.. 949 records from Percentage analysis of dinoflagellate cyst taxa groups from surface sediment samples of the eastern Indian Ocean. 1 records from Zur Kenntnis der Lithobiiden. 19526 records from Wildbook for Whale Sharks. 7 records from Cordylancistrus nephelion (Siluriformes, Loricariidae), a new and endangered species of suckermouth armored catfish from the Tuy River, north-central Venezuela.. 405 records from (Table 5) Range chart of benthic and planktonic foraminifera of ODP Site 127-797. 68 records from RSPB - Bean geese on the Slamannan Plateau, Central Scotland between 1993 and 1995 (RSPB/SNH/Bean Geese Action Group). 419514 records from Meadow and Pasture Inventory (SJV). 212 records from (Appendix A) Campanian-Maastrichtian calcareous nannofossils in DSDP Hole 44-390A. 7046 records from HFSL - Herbário Dr. Ary Tupinambá Penna Pinheiro. 105 records from (Table 1) Occurrence of Early Cretaceous foraminifers and radiolarians in ODP Hole 130-807C. 84521 records from BioGIS - Vascular plants - INPA database. 9526 records from UK Cetacean Strandings Investigation Programme - Stranded cetacean data from Great Britain collected from 01/01/89 through to 31/03/10. 23 records from Trichoribates and Jugatala (Acari: Oribatida: Ceratozetidae) from the Central and Southern Alps, with notes on their distribution. 1 records from Campylomorphus homalisinus (Elateridae): a new species for Lombardy (Italy), with notes on its ecology, distribution and biogeography. 4611 records from DMNS Marine Invertebrate Collection (Arctos). 1 records from Über einige von Jaroslav Storkán in Bulgarien gesammelte Chilopoden. 1447 records from Odonata of the Congo River 2010 expedition. 690 records from Field Study Group of the Dutch Mammal Society (NL) - 2012 - Mammal Survey Galicia, Spain. 8780 records from HPBR - Herbário Padre Balduino Rambo. 131642 records from mel. 1 records from Report on the occurrence of synanthropic derived form of Chrysomya megacephala (Diptera: Calliphoridae) from Royapuram fishing harbour, Chennai, Tamil Nadu, India. 8441 records from Natural England - Batsites inventory for England. 201581 records from CAS Ichthyology (ICH). 24 records from A new species of Jenynsia (Cyprinodontiformes: Anablepidae) from northwestern Argentina and its phylogenetic relationships.. 13949 records from University of Amsterdam (NL) - Páramo Vegetation Research, Chingaza - Cruz Verde - Monserrate -Guasca, Colombia. 10 records from Ecsenius niue, new species of blenniid fish, and new distribution records for other species in the Opsifrontalis species group.. 258 records from Banco de Germoplasma de la Universidad Rey Juan Carlos. 78456 records from KUBI Vertebrate Paleontology Collection. 25128 records from rmca-albertine-rift-butterflies. 1 records from Nothrus piceus. 18 records from (Table 3) Foraminiferal species in DSDP Sample 78-541-5-3,19-21. 761 records from Dorset Environmental Records Centre - Dorset Heath - NBN South West Pilot Project Case Studies. 85 records from Ober-Olmer Wald. 10000 records from Coleccion Entomologica CEI - CCT Mendoza CONICET.. 28 records from (Table 2) Distribution of the endemic fly (Anatalanta aptera) and the introduced ground beetle (Merizodus soledadinus) on the Kerguelen Islands. 600 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Accipitridae. 161 records from (Appendix A) Planktonic foraminifera abundances in ODP Site 138-852B. 613 records from Countryside Council for Wales - Shad Monitoring data. 5459 records from Diptera collection (ED) of the Muséum national d'Histoire naturelle (MNHN - Paris). 20 records from Botia udomritthiruji, a new species of botiid loach from southern Myanmar (Teleostei: Botiidae).. 6033757 records from NMNH occurrence DwC-A. 69 records from Occurrence data of Namadytes (Diptera: Asiloidea: Mydidae). 855 records from (Table 1) Distribution of ostracods in Jurassic sediments of DSDP Hole 79-547. 73167 records from ALCB - Herbário Alexandre Leal Costa. 4959 records from HUSC - Herbário Unisanta. 34829 records from Fish Collection - Instituto Nacional de Pesquisas da Amazônia (INPA). 195867 records from UAM Herbarium (ALA), Vascular Plant Collection (Arctos). 121 records from (Table 2) Relative contents of planktonic foraminifera in bottom sediments from the Ashadze-1 Hydrothermal Field. 544 records from Glasgow Museums BRC - The Changing Flora of Glasgow: Orchid Dataset. 1489 records from Herbarium Rhoenmuseum Fladungen. 1266 records from Actinomycetes Collection in BCRC. 23215 records from Monitoring data from the federal state Rhineland-Palatinate (Germany). 16572 records from Visdoorgangen - Fish passage places in Flanders, Belgium. 923 records from Colección Plantas Vasculares - Herbario del Departamento de Biología, Bioquímica y Farmacia de la Universidad Nacional del Sur. 9 records from Trichomycterus pauciradiatus, a new catfish species from the upper rio Paraná basin, southeastern Brazil (Siluriformes: Trichomycteridae).. 22224 records from Monitoring data from the federal state Mecklenburg-Western Pomerania (Germany). 27299 records from NCSM Vertebrate Paleontology Collection. 428264 records from Essig Museum of Entomology. 45 records from Université Pédagogique Nationale de Kinshasa (UPN) - Le bétail dans la République Démocratique du Congo (bases de données des animaux élevés pour consommation)- Projet CABIN. 2 records from Acrochordonichthys gyrinus, a new species of akysid catfish (Teleostei: Siluriformes) from Thailand.. 987 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Thraupidae. 18004 records from Census of the animals of Benin. 6 records from First record of Tettigettalna mariae (Quartau & Boulard 1995) (Insecta: Hemiptera: Cicadoidea) in Spain. 1 records from On the Chilopoda from Turkey. 10234 records from Collection entomologique Barthélémy. 11 records from Himantura hortlei n. sp., a new species of whipray (Myliobatiformes: Dasyatidae) from Irian Jaya, Indonesia.. 1 records from Pollen analysis of sediment profile BLA00 from Blankensee. 87 records from Tab. 5: Artenzusammensetzung, mittlere Individuendichte, Diversität und Eveness der benthischen Gemeinschaft. 61468 records from Naturalis National Natural History Museum (NL) – Aves_ Passeriformes. 169 records from Record of 7 acritarch taxa, and palynological preparation data from the Miocene, Pliocene and Pleistocene of DSDP Hole 93-603C. 1440 records from (Table 21) Benthic foraminifera in middle Miocene sediments of DSDP Hole 90-594. 39766 records from BioGIS - Vascular plants - A. Danin's point database. 17447 records from Swedish Board of Fisheries (Fiskeriverket) - National Register of Survey testfishing. 1353 records from Composición florística y estructura de una parcela permanente en bosques secos tropicales del municipio de Santa Fé de Antioquia, Antioquia (primer censo). 33 records from (Table 2) Distribution of Cretaceous redeposited benthic foraminifers at DSDP Hole 89-585A. 7 records from (Table T4) Nannofossil counts accross the K/T boundary in ODP Hole 183-1138A. 7356 records from Cumbria Biodiversity Data Centre - Cumbria Biodiversity Data Centre. Moss and Liverwort Observation Records. Pre-2010 for Cumbria. 819 records from Inventaire National du Patrimoine Naturel : CBN de Midi-Pyrénées. 208 records from (Table 4) Distribution of recurrent benthic foraminifera at DSDP Hole 75-530A, from Campanian and Maestrichtian. 31 records from First description of the worker caste of Nylanderia smythiesii (Hymenoptera: Formicidae). 39 records from ECOCEAN MantaMatcher. 3327 records from BioGIS - Mammals - SPNI. 1 records from Nothrus biciliatus. 2432 records from RSPB - Black Grouse Recovery Project Annual Survey in Argyll & Bute 2002-2009 (RSPB/SNH/FCS/Scottish Power). 91 records from (Table T2) Paleocene calcareous nannofossil abundance of ODP Hole 173-1068A. 247 records from Quirópteros Asociados al Bosque Seco de la Vereda El Carbonero, Santander de Quilichao, Cauca. 1 records from Nothrus mutilus. 252125 records from Moths Ireland. 1166 records from Colección de Saurios Museo de La Salle Bogotá (MLS). 1915 records from Colección de Anfibios Museo de La Salle Bogotá (MLS). 14605 records from DMNS Mammal Collection (Arctos). 129 records from Mammalia (KNAM-MM). 25883 records from Monitoring data from the federal state Saxony (Germany). 6 records from Succession of benthic hard-bottom communities abundance at X-Huinay in 2011. 4 records from Ameisen von Madagaskar, den Comoren und Ostafrika.. 3 records from Achaeta becki sp. nov. (Oligochaeta: Enchytraeidae) from Amazonian forest soils. 2052 records from Angelo State Natural History Collections (ASNHC) - Ornithology Collection. 124 records from Birdrace-Die_Ackermännchen-Schalm-Eder-Kreis. 150 records from Birdrace-Ostseevögel-Ostvorpommern. 109 records from Birdrace-Di_Bi_Di_Birder-Wesel. 27 records from Tejidos de anfibios y reptiles de la ventana piloto Paz de Ariporo - Hato Corozal. 660 records from (Table 1) Benthic foraminifera in late Miocene sediments of DSDP Hole 89-586B. 5450 records from Collection paléontologique du Museum d'histoire naturelle de la ville de Bourges (BOUM). 4 records from Pollen analysis of sediment profile WO1 from Wollingster See. 376 records from (Table 1) Distribution of planktonic foraminifera in the Cretaceous succession of DSDP Hole 95-612. 523 records from Aves Argentinas / Asociación Ornitológica del Plata - Colección de registros observacionales de aves silvestres argentinas - Lista Narosky: familia Ardeidae. 57495 records from TNHC Ichthyology Collection. 96 records from (Table 2) Neogene benthic foraminiferal community at DSDP Hole 95-613. 638 records from EcoRecord - Fish records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 128 records from Birdrace-Brut-Wetteraukreis. 168 records from Birdrace-Marburger_Vogelwelt.de-Marburg/Biedenkopf. 25 records from Countryside Council for Wales - Freshwater Gwyniad Survey Data. 96 records from Birdrace-federleser-Herford. 90 records from Birdrace-Uttenreuther_Spatzenzähler-Erlangen/Höchstadt. 102 records from Birdrace-Die_Nachtraben-Stuttgart. 185 records from Klasse 3a. 122 records from Kloster Eberbach. 97 records from LauWi. 70 records from Gewässer des Wartbergparks Stuttgart (bei der Ökostation der VHS Stuttgart). 28 records from The land crab Johngarthia planata (Stimpson, 1860) (Crustacea, Brachyura, Gecarcinidae) colonizes human-dominated ecosystems in the continental mainland coast of Mexico. 128787 records from Seed and Leaf Beetle Recording Scheme - Bruchid and Chrysomelid Distributions in Britain and Ireland: pre 1900, 1900-1979, 1980 onwards. 122 records from Birdrace_Gütersloher_Gimpel-Gütersloh. 123 records from Birdrace-Thüringer_Becken-Sömmerda. 19451 records from Herbarium of the Department of Natural Forests (Forest Research Institute). 120 records from Birdrace_Steckbyer-Auenländler-Anhalt_Zerbst. 114 records from Birdrace-Finkenspötter-München. 110 records from Birdrace-LiLaMai-Vechta. 100 records from Birdrace-Meister_der_Herzen-Kleve. 91 records from Birdrace-Die_TUErteltauben-Tübingen. 92 records from Birdrace-Team_BO-bachter-Bochum. 127 records from Birdrace_Schräge_Vögel-Herford. 88 records from Birdrace-WeserEggeLäufer-Höxter. 84 records from Birdrace-Haubenpirole_vom_Biomarkt_West-Tübingen. 67 records from Birdrace-Guckers_Offenbach-Offenbach. 71 records from Birdrace-NAJU_Aspach-Rems/Murr. 74 records from Birdrace_Gätkes_Schergen-Helgoland. 151 records from Isarufer. 1836 records from (Figure 2) Occurrence of planktonic foraminifers and other selected constituents in samples from DSDP Hole 80-548. 1487 records from (Appendix A) Relative abundance of planktonic foraminifera in ODP Hole 117-723A. 2 records from Filling in the gap: two new records and an updated distribution map for the Gulf Sand gecko Pseudoceramodactylus khobarensis Haas, 1957. 209 records from (Appendix A) Palynofacies absoulte abundances of DSDP Hole 38-338. 120 records from Birdrace-Kosmos_Racer-Freising. 118 records from Birdrace-Birding_Bentheim-Grafschaft_Bentheim. 118 records from Birdrace-Blind_vor_Birds_BVB_Kranenburg07-Kleve. 2413 records from Literature based species occurrence data of birds of North-East India. 112 records from Birdrace_Die_Borner-Viersen. 111 records from Birdrace-Uhulogen-Lippe. 109 records from Birdrace-Team_Charadrius-Günzburg. 108 records from Birdrace-TriumVIErat-Viersen. 105 records from Birdrace-ARKONAuten-Rügen. 102 records from Birdrace-Westfälische-Nachtigallen-Recklinghausen. 104 records from Birdrace-Diesmal_sehen_wir_mehr-Lippe. 103 records from Birdrace-Borussia_Zippammer-Bad Kreuznach. 104 records from Birdrace-RMD_Die_Gipfelstürmer-Main-Taunus-Kreis. 101 records from Birdrace-Herford-Birder-Herford. 97 records from Birdrace-Die_Bonnapartemöwen-Rhein-Sieg-Kreis. 95 records from Birdrace-Buteo1_DO-Dortmund. 55 records from Waldsee. 99 records from Birdrace-Die_EderSeaWatchers_WsndaH!-Waldeck/Frankenberg. 103 records from Birdrace-Die_Nachtigallen-Herford. 72 records from Birdrace-Buteo2DO-Dortmund. 59 records from Im Bauerngarten. 33 records from (Table 1) CTD data, mean spring and annual temperatures and salinities from World Ocean Atlas (WOA, 2001), and Mg/Ca data, sampled with a multinet at station 74 and 81 from RV Poseidon cruise 334. 137 records from VFD-H: Rheingau: Pferdeweide Loock. 241 records from BIRDRACE RennVögel Münsterland. 162 records from Siegen/ Gymnasium Am Löhrtor. 34 records from Borkhart. 198 records from FNL e.V.. 83 records from Spechtwald. 271 records from Beweidungsprojekt an der Nesse. 114 records from Flora. 100 records from Feriendorf Ober-Seemen. 105 records from Feriendorf des Kreises Gedern (Ober-Seemen). 94 records from Birdrace-Resopal_Altkreis_Dieburg-Team-Darmstadt/Dieburg. 91 records from Birdrace-Enger_am_Spektiv-Herford. 85 records from Birdrace-Die_Paradiesvögel-Herford. 81 records from Birdrace-Breisgau_Brut-Breisgau/Hochschwarzwald. 76 records from Birdrace-Birding_for_Nature-Bonn. 2818 records from Araneae collection (AR) of the Muséum national d'Histoire naturelle (MNHN - Paris). 257 records from Seewasen. 360 records from Küstenschutzwald. 88 records from Birdrace_Die_Polyglotten-Saarlouis. 50805 records from Plant Specimen from Herbarium (NAS) in China, Institute of Botany, Jiangsu Province and Chinese Academy of Sciences. 144 records from Ehmkendorf. 100 records from Grenzturm Hohen Neuendorf. 52 records from Fledermaus. 271 records from Dierloch, nördlicher Mooswald (Freiburg-Hochdorf). 57 records from Heidesee / Halle. 5036 records from Herbarium specimens of Association des Naturalistes de la vallée du Loing (ANVL). 23 records from Alter Nördlicher Friedhof (München). 2 records from Pollen analysis of sediment profile KAI2 from Kaiserwinkel. 342 records from Kremmer Luch. 155 records from Hainhoop - Tonkuhle - Bullenmoor (Arpke). 55 records from Von A(horn) bis Z(ecke) des WWP Chemnitz. 44 records from "Schlechteberg" Ebersbach/Sa.. 103 records from Fuchsloch (Mohlsdorf/Ostthüringen). 97 records from Döchtbühlwald (Bad Waldsee). 233 records from Föhrenried (Fronreute und Baindt). 15 records from AKG-Bensheim. 80 records from Förderzentrum Schmölln. 245 records from Kiesgruben Wemb. 57 records from Waldhusener Moor (Lübeck-Kücknitz). 263 records from Artenvielfalt Kreis Gießen. 74 records from Lebensraum Fluß/Zwickauer Mulde in Wolkenburg. 98 records from Rund ums Cani. 70 records from Lech 2001. 113 records from Hochschulgelände (Bremen). 37 records from Berlin - Treptower Park / Karpfenteich. 101 records from Naturgrundstück (Eutin). 69 records from Lassentiner Moor (Niepars). 28 records from Hecke - Klassen 2 a und 2 b VS Tussenhausen. 195 records from Truppenübungsplatz Panzerkaserne Böblingen. 69 records from Schulgarten mit Klasse 8a (Essen). 84 records from Roter Berg Werdau (Leubnitz). 270 records from Regenrückhaltebecken (Zeulenroda). 69 records from Kinder- und Jugendferiendorf des Kreises Groß-Gerau - Gedern/Ober-Seemen. 282 records from Deponie Klausdorf. 313 records from Stadtpark Herzberg (Elster). 167 records from Zielbach (Töll). 45 records from Flusswerder in der Weser (Hameln). 56 records from Zitadelle Berlin-Spandau (7b). 158 records from Panke und Ufer am Kinderbauernhof Pinke-Panke. 54 records from Wiese am Unterbecken. 52 records from Caracterización vegetal de una zona de alta montaña (litoral de San Juan) como herramienta de proyección para el establecimiento de una figura de conservación en el chocó biogeográfico. 27 records from Laubwald Dreiländereck (Aachen/Vaals[NL]). 20 records from Motzener Tonsee. 248 records from Verwilderter Hausgarten mit angrenzendem Gelände (Laufenburg-Hochsal). 325 records from Triebesbach (Zeulenroda-Triebes). 41 records from Örtzemündung (Stedden). 96 records from Die Wuhle. 1 records from Oribates mollicomus. 6 records from Der Wiesenpark in Oschersleben - ein Arboretum mit eigener Ästhetik. 65 records from Gemeinschaftsgarten Deluxe (Bernburg). 64 records from Kabelskebach (Kabelsketal, Saalkreis). 57 records from verschiedene Kleingewässer um Oldenburg/Holstein. 10 records from Kita-Wäldchen Fuchsturmweg Jena. 161 records from Schussenaue bei Berg. 304 records from Ried und Sand - Artenvielfalt durch Beweidung. 85 records from Insektenvielfalt Ahe/Weichelsee. 122 records from Stever. 12 records from Kindergarten. 79 records from GymnQuerfurt. 43 records from Gewässeruntersuchung Grötzinger Baggersee. 153 records from Landschaftsschutzgebiet "Holmer Sandberge". 108 records from Mainufer. 163 records from Brander Wald (Stolberg). 212 records from Artenvielfalt im Beckerbruch (Dessau). 103 records from Wasserwerkspark (Chemnitz). 99 records from Düne am Ulvenberg (Darmstadt). 28 records from Sandgrube Zaisertshofen. 248 records from Herrensee-Gebiet (Fischbachtal im Odenwald). 13 records from Botia kubotai, a new species of loach (Teleostei: Cobitidae) from the Ataran River basin (Myanmar), with comments on botiine nomenclature and diagnosis of a new genus.. 111 records from Ökologischer Weinberg (Guntersblum). 26 records from Quellgebiet Flossach - Klassen 4 a und 4 b VS Tussenhausen. 130 records from Schulgelände Gebrüder-Grimm-Schuleund Umgebung (Lingen). 108 records from Gelände der Lahntalschule Biedenkopf und Lahnauen. 86 records from Besonderer Ort - besondere Natur: Die Mainzer Zitadelle. 66 records from Wedeler Au. 170 records from Bodenseeufer Radolfzell. 150 records from Steinbruch Mainz-Weisenau. 36115 records from Colección Nacional de Invertebrados - Museo Argentino de Ciencias Naturales 'Bernardino Rivadavia'. 22 records from Dellwiger Bach (Dortmund). 69 records from "Schwarzes Teich" (Waldpark Radebeul). 375 records from Lillachtal mit Kalktuffquelle bei Weißenohe. 79 records from Balkon (Norderstedt). 39 records from Südpark (Bochum-Wattenscheid). 95 records from Ortelsbruch - Hangmoor bei Morbach. 46 records from Hainbachtal in Oelsnitz/V.. 219 records from Umgebung der Grundschule Oderberg. 149 records from Wirbach. 183 records from Westerwälder Umwelt- und Naturschutztag Limesgemeinde Hillscheid. 86 records from Alter Kreidebruch Saßnitz/Rügen. 113 records from Rund um das LUGY. 308 records from Wangerooge. 101 records from Naturhausgarten. 65842 records from Fungus Collections at Staatliches Museum für Naturkunde Karlsruhe (Herbarium KR). 253 records from Geschützter Landschaftsbestandteil - GLB "Troppach". 180 records from Paul-Gerhardt-Schule Dassel. 145 records from privater Garten. 181 records from Spießwoogtal / Königsbruch (Fischbach). 192 records from Steinbruch Mainz-Weisenau, 2. Jahr. 112 records from CommunicA Koblenz - Wildkräuterexkursion - Rheinsteig Bornhofer Höhe. 264 records from Natur erleben rund um den Seminarbauernhof Gut Hohenberg. 31 records from Nationalpark Harz Schul-AG Braunlage. 106 records from Schulgarten Hans-Carossa-Oberschule. 107 records from Landschaftsschutzgebiet Buchhorst 3. 117 records from Wassermann. 9 records from Willersalpe. 54 records from Zentralfriedhof (Wien). 63 records from Erft in Selikum (Neuss). 73 records from Varnhalt. 59 records from Rund ums Ökohaus (Würzburg). 50 records from Junge Heide, Radebeul/Dresden. 18 records from Spielwiese. 124 records from Wiesenbiotop am Wasserturm. 18 records from Dachterasse Realschule St. Bernhard (Bad Mergentheim). 103 records from Schwanseepark (87645 Schwangau). 107 records from Biotop Binsenwiesen und Ernst-Reiter-Wiese (Wehrheim/Taunus). 1037 records from Countryside Council for Wales - Rare Flowering Plant and Fern Data. 40 records from Streuobstwiesengelände St.Meinrad Gymnasium. 82 records from Rückkehr der Biber in Rheinland-Pfalz - Biber in der Primmerbach. 54 records from Ludwigshofen. 71 records from Bolzplatz. 18 records from Mittelstreifen. 35 records from Urwald 3 (Bad Waldsee). 41 records from Wiese und Bach beim Unterbecken (Markersbach). 17 records from Schutzgebiet Ochtersum. 171 records from Biodiv-Camp Sandmagerrasen in Nürnberg/Langwasser. 32 records from Schulhof Sandhofenschule (Mannheim). 160 records from Wirbach-Taubental (Bad Blankenburg). 34 records from Hangwiese bei Tussenhausen Klassen 1 a und 1 b. 77 records from Trockenrasen Franzigmark (Halle/Saale). 40 records from Schulhof Liebfrauenschule Oldenburg. 48 records from Trockenrasen bei Dörndorf. 49 records from Schulgartengelände des Hans-Carossa-Gymnasiums (Berlin). 303 records from Garten J. Scherrer (Lachen-Speyerdorf). 28 records from ISTOTA - Schulgarten in Krakau, Stadtteil Ludwinow. 50 records from Artensuche auf den Elbwiesen in Radebeul. 81 records from Umgebung des Spalatin Gymnasium Altenburg. 74 records from Naturschutzgebiet Lippeaue (Marl) - Pfadis in Sickingmühle. 297 records from Naturparadies in Gräfenhausen am Trifels (bei Annweiler). 61 records from Artenvielfalt auf der Wiese. 55 records from Flora und Fauna am Mittelrheintal. 95 records from Vielfalt verschiedener Wiesen. 53 records from Weidegut Rechab. 68 records from Schulhof der Astrid-Lindgren-Schule (Elmshorn). 104 records from Außengelände KITA "Mäuseburg" Waldkirchen. 194 records from Landschaftsschutzgebiet Eulenkopf (VG Otterbach). 233 records from Borstgrasrasen um die Burg Baldenau im Oberen Dhrontal. 244 records from WildesMoor bei Schwabstedt. 4 records from Arthropoden aus südostalpinen Höhlen.. 5 records from Streuobstwiese (Mittelgasse 4). 99 records from Dorfrand Mauderode. 97 records from Natur-Erlebnis-Kindergarten Waldkirchen/Erzgebirge. 153 records from Selztal bei Friesenheim. 163 records from Schulhof der Astrid-Lindgren-Schule Elmshorn. 40 records from Flächennaturdenkmal Grubditz. 58 records from Weidewirtschaft. 92 records from Birkenloh. 881 records from Moluscos Marinhos de Augusto Nobre. 94 records from Kochertgraben II. 57 records from Garten in Schmölln. 65 records from Mauernacker (Wettsaasen). 62 records from Tag der Artenvielfalt BUND Kaiserslautern. 22 records from Heilpflanzen im Hainbachtal. 59 records from Oschenberg, NO von Bayreuth-Laineck. 98 records from Warnowtal (Rostock). 120 records from Naturschutzgebiet Lochbusch-Königswiesen. 60 records from Schafsweide Seniorenhaus Berghof. 20 records from Hübsche Kröten, Wetterfrösche und andere Froschnaturen. 110 records from Obstwiese Osterberg. 25 records from Aachen: Exkursion essbare Wildkräuter/UTROPIA. 16505 records from Conchological Society of Great Britain & Ireland - Mollusc (non-marine): Compilation of records of rare and scarce species for Great Britain and Northern Ireland. 4 records from Schulbiotop und Brigach (Villingen). 19 records from Goethe-Hauptschule/Projekt I-10. 51 records from Revision of the Nearctic endemic Formica pallidefulva group.. 28 records from Uferzone Wipper (Biesenrode). 22 records from Breitkopfbecken (Berlin-Reinickendorf). 139 records from NSG Leist bei Ziegenhain. 245 records from Gieselbachtal Fulda-Harmerz. 43 records from Saalewiesen Naumburg. 51 records from Schrebergarten Düsseldorf Oberkassel. 30 records from NABU VG Weilerbach - NSG Mehlinger Heide, FFH-Gebiet. 62 records from Amtsrain Apolda-Zottelstedt. 43 records from Schulgelände Thurmair-Gymnasium. 28 records from Hainbachtal bei Oelsnitz / V.. 48 records from Weide am Ostufer des Zotzensees, Müritz-Nationalpark. 214 records from Binsenwiesen. 82 records from Mainfränkischer Trockenrasen und Naturschutzgebiet Höhfeldplatte bei Veitshöchheim. 172 records from Dalbekschlucht. 2 records from Oribatids from Switzerland VII (Acari: Oribatida: Mycobatidae 1) (Acarologica Genavensia XCIX). 16 records from A review of the systematics of western North Pacific angel sharks, genus Squatina, with redescriptions of Squatina formosa, S. japonica, and S. nebulosa (Chondrichthyes: Squatiniformes, Squatinidae).. 47 records from Neanderthal. 166 records from Steinbruch Mainz-Weisenau, 3. Jahr. 87 records from VFD-H: Heidenrod: Pferdeweide Mürth. 69 records from Entdeckertour am Muldestausee 1/05. 9871 records from Dumfries and Galloway Environmental Resources Centre - Micro-moths distribution for Dumfries and Galloway. 127 records from Birdrace-Alb_Donaumoos_Kompetänzteam-Alb-Donau-Kreis. 172 records from Leben im Finkensteiner Moor. 5 records from Naturschutzgebiet Ahrmündung (Remagen). 54 records from Bäche, Quellen und Teiche im FFH-Gebiet Mühlhauser Halde. 169 records from Birdrace-Cuxland_Schwenke_GeoConsult-Cuxhaven. 122 records from Birdrace-Hügelland-Mainz/Bingen. 101 records from Isartal Dingolfing. 160 records from Waldstück Bremerhagen LK Bio Kl. 12. 107 records from vegoek. 98 records from Gewässer des Wartbergparks Stuttgart (beim Naturlabor der Umweltakademie Baden-Württemberg). 46 records from (Table 4) Biomass of (benthic) amphipods in the Bering and Chukchi seas. 97 records from Landschaftspark St.Leonhard-Deisendorf. 113 records from Staatsforst Rehna - Woitendorfer Wald im Biosphärenreservat Schaalsee. 62 records from Zoo Frankfurt. 147 records from NABU-Auerochsenweide. 93 records from Höltigbaum. 80 records from VFD-RP: Taunus: Ponykoppel Thurner. 63 records from Hochschule Zittau/Görlitz. 61 records from GE-Brühl. 86 records from Naturerlebnisraum Koppelsberg (Plön). 257 records from Dinocyst occurrences and zonations from IODP Hole 313-M0028A. 207 records from Biosphäre Bliesgau. 60 records from NABUGEO1. 40 records from Öhmdwiesen und Göldern (Konstanz). 3 records from New synonym of Tipula (Vestiplex) wahlgrenana Alexander, 1968 (Diptera: Tipulidae). 141 records from Birdrace-Asiola_Quartett-Nordwestmecklenburg. 15 records from Regenwasserabfangsbecken (Erlenbach). 193 records from Gelände des Schulzentrums am Himmelsbarg. 54 records from Weidegebiete in der Selzrenaturierung. 110 records from Birdrace-Göttinger_Sozialbrachvögel-Göttingen. 39 records from Soolbach-Tal. 120 records from Birdrace-The_early-Birds-Minden/Lübbecke. 46 records from 8c. 1894 records from Colección viva Jardín Botánico Universidad Tecnológica De Pereira. 10 records from Feuchtwiesen Wippertal bei Wippra. 134 records from Birdrace-Team_Havelland-Havelland. 155 records from Birdrace-Usedommeln-Ostvorpommern. 110 records from Birdrace-Alle_Vögel_sind_schon_DADA-Uckermark. 133 records from Wulfsmuehle/Pinnau. 87 records from Hartholzaue an der Dreisam (Freiburg/March-Hugstetten). 217 records from Birdrace-Ornis_im_Einsatz-Lahn-Dill-Kreis. 100 records from Birdrace-ImmerWiederhopf-Lörrach. 57 records from Schulgarten Fichteschule. 81 records from Artenvielfalt im Schlosspark Sayn (Sayn/Bendorf). 70 records from Birdrace-WdW-Wilder_Westen-Viersen. 51 records from Steinbachtal (Würzburg). 66 records from Schulhof A.-Lindgren-Schule (Elmshorn). 81 records from Stadtpark Schmölln. 58 records from Schulhof der Astrid-Lindgren-Schule und Umgebung (Elmshorn). 22 records from Kuhwiese Beerentaltrift (Hamburg/ Harburg). 128 records from Birdrace_turbine_untersee-Konstanz. 94 records from Birdrace-Erlanger_Piepmätzchen-Erlangen/Höchstadt. 12 records from Naturschutzgebiet Swistbachaue (Eckendorf). 118 records from Birdrace_FliegendeFüchseLBSGescher-Münster. 100 records from Birdrace-The_Ringers-Friesland. 281 records from Hertfordshire Biological Records Centre - Hertfordshire Wildlife Site Monitoring Surveys (incomplete). 96 records from Birdrace-Berlin_Sparrows-Uckermark. 299 records from (Tables 1-15) Morphometric characteristics of the genus Hinia (Nassariidae, Gastropoda) in the Tertiary of northwest Germany. 77 records from Birdrace-Naturschutzscheune-Darmstadt/Dieburg. 83 records from Birdrace-Team_Eckhard_Reinstein-Hersfeld/Rotenburg. 23 records from Wiese Niederaula. 89 records from Birdrace-Team_Wangerooge-Friesland. 102 records from Industriebrache (Kempen). 31 records from Kurler Busch (Scharnhorst). 12 records from Anatomical investigation of the slender catshark Schroederichthys tenuis Springer, 1966, with notes on intrageneric relationships (Chondrichthyes: Carcharhiniformes: Scyliorhinidae).. 142 records from Kinderbauernhof Pinke-Panke. 85 records from Birdrace-Halsbandschnäpper-Stuttgart. 79 records from Birdrace-Bielefinken-Bielefeld. 42 records from sbosch. 83 records from Birdrace-Die_Vogelscheuchen-Herford. 53 records from Birdrace-Die_Tigerenten-Erlangen/Höchstadt. 102 records from Birdrace-OAG_Neuwerk-Hamburg. 53 records from Bad Bodenteicher Heide. 13 records from Garten Hamburg Uhlenhorst. 36 records from Selz (Ingelheim am Rhein). 31 records from Blumenwiese und Heckensaum , Kornberg (Gruibingen). 26 records from Kinderbauernhof Pinke Panke - Berlin Pankow. 74 records from Steinberg in Heidelberg-Handschuhsheim/Falgen. 65 records from LSG "Großes Bruch". 48 records from Morphologische Daten von Natrix. 21 records from Bach. 63 records from Sternwiese Mülheim-Broich. 81 records from Birdrace-Die_Ornithomaten-Herford. 78 records from Birdrace-Die_Laufenten-Braunschweig. 24 records from Schulhof der Hermann-Runge-Gesamtschule (Moers). 47 records from Revised diagnosis of the genus Bangana Hamilton, 1822 (Pisces: Cyprinidae), with taxonomic and nomenclatural notes on the Chinese species.. 1346 records from EcoRecord - Fungi & Lichen records held by EcoRecord for the Birmingham and the Black Country area collated prior to March 2013. 39 records from Stausee Weiditz. 28 records from Schulgelände Freiherr-vom-Stein-Gymnasium (Hamm). 221 records from Römertal (Steinpleis). 29 records from Naturerfahrung. 31 records from Regenwasserabfangbecken. 4472 records from MVZ Bird Observations (Arctos). 36 records from Feuchtbiotop, Wildtier- und Artenschutzstation Sachsenhagen, Sielmanns Natur-Ranger. 64 records from Schafheide im Böblinger Wald. 64 records from Pilzlehrwald. 21 records from Tauchen und Meer 02. 35 records from Gym Freyung. 51 records from Mühlenbach bei Buxtehude. 102 records from Spreewaldfließe und Feuchtwiese bei Lübbenau. 56 records from Estetal (Buxtehude). 27 records from Zwickau- Schwanenteich. 23 records from AKG-Gelände in Bensheim. 23 records from Ackerrain Plönhagen. 19 records from Glemstal (Leonberg). 16 records from Streuobstwiese Am Kalkofen, Hirschhorn (Kreis Kaiserslautern). 44769 records from University of British Columbia Herbarium (UBC) - Lichen Collection. 21 records from Riedkanal Bötzingen. 829 records from Cambridgeshire & Peterborough Environmental Records Centre - Chippenham Fen Moth surveillance project. 53 records from Alter Lagerplatz und Gartenteich (Dortmund/Hörde). 36 records from Plöwener Wald. 45 records from Schulgelände Hans-Carossa-Gymnasium (Berlin). 27 records from Vögel. 36 records from Ruhrwiesen Arnsberg, Klasse 9 und 10, Fachbereich Biologie. 141 records from Draubiotop Lavamünd. 57 records from Mauervegetation,Flechten und anderes. 24 records from Schulgelände der Waldorfschule Vordertaunus in Oberursel. 5 records from Gewässeruntersuchung (Prien) mit Kl. 4b. 36 records from Olympiapark (München). 24 records from Kaisertal. 7 records from Schulhof A.-Schweitzer Schule (Wetzlar). 36 records from Salzwiese Diekskiel. 6 records from Fließgewässeruntersuchung am Haselbach. 5 records from Naherholungsgebiet Lange Erlen (Riehen/Basel). 5 records from Feuchtwiese. 8 records from Krittenhorster Wald (Ostkilver). 71 records from Birdrace-do_elster_Dortmund. 87 records from Klütwald. 54 records from Park Schönfeld (Kassel). 49 records from Dörnberg. 47 records from Schulgelände Ceciliengymnasium. 117 records from Naturschutzgebiet Kochertgraben. 26 records from Erhard Sopp. 23 records from Schulgarten der Hainbuchenschule (Hagenbach). 66 records from Selz-Renaturierung (Hahnheim/Sörgenloch). 1174 records from Sudeniederung (Amt Neuhaus). 21 records from "Natur macht Schule 2" Natur im Wohngebiet Gorndorf. 28 records from Stadtpark Prinzengarten (Sigmaringen). 4 records from Weser und Weseraue bei Höxter, Godelheim und Boffzen. 721 records from IBF Monitoring of Plant Galls. 9 records from Wiesendreieck Luckenwalde. 67 records from Weide an der Mosselde / Dortmund-Kirchlinde/Westerfilde. 36 records from Mittelriede Höhe Gliesmarode-Braunschweig. 39 records from Regenrückhaltebecken Bad Bevensen. 15 records from Die geheimnisvolle Welt der Spinnen. 84 records from Streuobstwiese Haus Zeitz. 101 records from Hoher Stein Kallenhardt. 22 records from Bachabschnitt der Nette (Osnabrück). 15 records from Naturschutzgebiet Ahrschleife (Altenahr). 11 records from Waldgebiet Todtnau- Sonnhalde. 81 records from Schulgarten-St.-Georg-Gymnasium. 26 records from Schulteich Heinrich-Mann-Schule. 32 records from Nationalpark Harz Juniorranger. 5 records from Inventur der Natur rund ums NABU-Naturzentrum in Haseldorf. 68 records from Streuobstwiese. 29 records from Brenz (Heidenheim). 36 records from Schulgelände Lise Meitner Realschule (Paderborn). 15 records from Beisetal bei Niederbeisheim. 709 records from Upper Silesian Museum, Bird Collection. 23 records from Tümpel Schulbiologiezentrum. 13 records from Eintauchen in die Natur /Harraser Weg (AWO - Kita Oberheldrungen). 13 records from Kleinsäuger der Mergelgruben Misburg (Hannover). 13 records from Warnowufer Groß Klein. 344 records from Meiofaunal abundance in sediments obtained during Belgica cruise BG06/13, Gollum Channels and Whittard Canyon. 17 records from Tierpark Zittau. 6 records from Sächsische Schweiz (Pfaffenstein). 41 records from Nachtaktiv im Ökogarten (Bad Waldsee). 11 records from Privatteich(St.Leon). 44 records from NW-Innenhof Gesamtschule Herten 7.6.2001. 18 records from Naturtag. 10 records from Bachpatenschaft Beeke. 1 records from Wiese, Wiesengebiet, Schiffdorfer Damm. 3 records from Blankenfelder See. 255 records from Colecciones Zoológicas de la Universidad de León, Colección de Bivalvos. 14 records from Three new species of the seasonal killifish genus Simpsonichthys, subgenus Hypsolebias (Teleostei: Cyprinodontiformes: Rivulidae) from the rio Paracatu drainage, rio São Francisco basin, Brazil.. 24 records from Ornithologische Wanderung um Tussenhausen. 27 records from Wiese hinter der Schule (Darmstadt). 8 records from Kleiner Ziergarten Winzingen (Neustadt). 7 records from Artenerhebung im Wiesenlautersystem/Pfälzerwald. 15 records from Bodentiere rund um die Schule. 15 records from Auf Feld und Wiese / Bretlebener Weg (AWO - Kita Heldrungen). 29 records from Insekten. 3 records from Naturschutzgebiet Quellgebiet Swistbach (Gelsdorf). 3 records from FFR Hausen. 45 records from Georgs-Padd (Wangerooge). 442 records from Nematode abundance in sediments obtained during RRS Discovery cruise D297. 22 records from Altendorfer Dorfbachhöhle / Sächsische Schweiz. 14 records from Lauchhamer GEO-Tag der Artenvielfalt. 2 records from Grenzdenkmal Hötensleben - wo früher Grenze wa(h)r - bewahrte Vielfalt. 27 records from Bäche im Mooswald (Vörstetten). 24 records from Tauchen und Meer. 15 records from Kirchheller Heide ( Bottrop). 11 records from Baumbach Arnsberg, Klasse 12, Fachbereich Biologie. 22 records from Kaltenkirchen Brache. 20 records from Mikroorganismen. 12 records from Kinderwald Hannover. 18 records from Wahner Heide - GK 12 Bio Gymnasium Köln-Deutz Thusneldastraße. 64 records from Wiese - Schulgelände des Franziskusgymnasiums (Lingen). 13 records from FND "Weißer Berg" Leißling. 8 records from Mit allen Sinnen durch den Wald / Schmücke (ev. Kita Heldrungen). 11 records from Kirschfest (Grundschule Heldrungen) / Kirschberg Oberheldrungen. 16 records from Im und um das Schulhaus. 42 records from Kleinstbiotop mit Schulteich/Weißwasser. 15 records from Hache im Ellernbruch (Sudweyhe / Weyhe). 12 records from Ohemoor (Hamburg/Norderstedt). 4 records from Sächsische Schweiz (Wehlener Gebiet). 12 records from Trockenmauern am ehemaligen Weinberg (Gelnhausen). 94 records from Landschaftsschutzgebiet Buchhorst 4. 5 records from Streuobstwiesengebiet (Kreis Ahrweiler). 40 records from Glacial cold-water coral: ages, isotope concentrations and ratios. 34 records from Wattenmeer-Safari (Wurster Watt). 40 records from Tiere und Pflanzen um uns herum !. 15 records from Tiere. 59 records from Schulteich Freie Waldorfschule Darmstadt. 16 records from Naturschutzgebiet "Gellener Torfmöörte" (Landkreis Wesermarsch). 7 records from Stadtrandlandschaft Apolda-Nord. 135 records from Waldi-Weiher. 1 records from Waldtag in und um Seelingstädt. 5 records from Schulhof Montessori Schule (Rotenburg / Wümme). 1 records from Haslauer Moor. 1120 records from Dpto. de Zoologia y Antropologia Fisica, Universidad de Murcia. 2814 records from GEO-Hauptveranstaltung im Nationalpark Bayerischer Wald. 371 records from Bannwald Burghauser Forst. 161 records from BIRDRACE Nord-Seh-Team. 369 records from BIRDRACE Havelland. 15339 records from Alterra (NL) - Comparison entomofauna in cities en countrysides. 17 records from Kohlbach (Sulzfeld). 15 records from Urwald 2 (Bad Waldsee). 11 records from Vögel im Garten Kindergarten Zaisertshofen. 2 records from Stadtrand Berlin - Altglienicke/ Was krabbelt auf unserem Abenteuerspielplatz?. 1 records from 5. Wiener Gemeindebezirk. 24469 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Anfibios. 91331 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Mamíferos. 555 records from FFH-Gebiet "Calwer Heckengäu". 13 records from Tag der Artenvielfalt am Bruckenwasen. 138 records from Artenvielfalt in der Stadt: Botanischer Garten Wuppertal und Hardt. 517 records from Schulzentrum "Parc Hosingen". 278 records from BIRDRACE Usedommeln. 89 records from BIRDRACE Hasenclevers Erben - NaBu-Bi-BirdRace-Open. 80 records from BIRDRACE Falkenberger Fluppis. 84 records from BIRDRACE Avinauten. 8 records from Eichendorf Weiher Schwalbach a.Ts.. 2 records from LSG Saale, Rößewiesen (Bernburg/Saale). 61 records from Rotes Steigle (Panzerübungplatz Böblingen). 5 records from Schulinnenhöfe (Gelsenkirchen). 9 records from Innenhöfe der Gesamtschule Berger Feld/ Gelsenkirchen. 2 records from Hildener Heide - Spörkelnbruch (Haan). 163 records from Tiere und Pflanzen am Pfannenbach. 6 records from Boimstorfer Sundern. 1 records from Karpfenteich, Klasse 6d. 5 records from Fledermäuse u. nachtaktive Insekten. 1 records from Fledermäuse über der Alster (Hamburg). 295 records from (Table 3) Range chart of benthic and planktonic foraminifera of ODP Site 127-795. 410973 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Aves Reproductoras. 37014 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Reptiles. 99 records from Schwanner Warte / Kinderhaus St. Elisabeth Waldplatz. 12 records from Schulgelände Erich-Kästner-Schule. 4 records from Neues Testprojekt. 174 records from Colecciones Zoológicas de la Universidad de León, Colección de Gasterópodos. 1462 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Flora Vascular Amenazada. 511 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Invertebrados. 16006 records from Ministerio de Medio Ambiente, y Medio Rural y Marino. Dirección General de Medio Natural y Política Forestal. Inventario Nacional de Biodiversidad 2007, Peces Continentales. 89 records from Schulgelände Paul-Gerhardt-Schule. 318 records from 10. GEO - Tag der Artenvielfalt 2008 - LSG "Pfarrhübel" Chemnitz. 61 records from Fürstenberger Ralley Teil 3. 15 records from Kühnauer Aue und Kühnauer See. 52 records from Naturschutzstation Weinberghaus (Dessau). 359 records from Pöhlberg bei Annaberg. 95 records from BIRDRACE BiBi. 95 records from BIRDRACE accipiter hardcore birding. 305 records from Rohrmeistereiplateau und angrenzendes Gebiet. 107 records from Müritz-Nationalpark. 1506 records from (Appendix C) Benthic foraminifera extinction group species in combined ODP Site 162-980 and DSDP Site 80-548. 447 records from Natur-Erlebnisgebiet der Naturschutz-Akademie Hessen und Umgebung. 1314 records from Biosphärenpark Wienerwald - Wiener Steinhofgründe. 93 records from Haarbach Höfe. 146 records from LK 11 im Mönchspark. 90 records from VFD-RP: Taunus: Kirchenweide Köpplers. 366 records from Weinberg Reichersdorf. 249 records from BIRDRACE DEVK-Deutschlands Enthusiastischste Vogel Kucker. 279 records from BIRDRACE Wannacks Topti(c)ker. 256 records from BIRDRACE Upupa epöpse. 254 records from BIRDRACE Thüringer Becken-Birders. 258 records from BIRDRACE Raumpatrouille Oriolus. 140 records from Waldfläche im Natur-Erlebnis-Pfad Pfinztal. 169 records from Expedition "Schulgelände". 74 records from Schulwald Grundschule Brügge. 126 records from Schulwald Marksuhl. 145 records from BIRDRACE Dith Marsh Sandpiper. 442 records from Inventaire National du Patrimoine Naturel : CBN Brest. 82 records from BIRDRACE Buteo2DO. 96 records from BIRDRACE Emslandracer. 102 records from BIRDRACE Westfälische Nachtigallen. 115 records from BIRDRACE Die UHULOGEN. 60 records from Pollen and age analysis of terrestrial plant wax from ODP Hole 175-1085A. 112 records from Kaniswall/ Gosener Wiesen an der Spree. 260 records from (Table T5) Biogenic and mineral composition of sediments cored in Westerland, Sylt. 274 records from Bernhardsthal. 106 records from VFD-RP: Eifel: Orchideenweide Ankly. 334 records from BIRDRACE Cuxland - Schwenke Geo Consult. 313 records from BIRDRACE Gätkes Erben. 269 records from BIRDRACE Kosmos-Racer. 97 records from BIRDRACE NABUhu Trier!. 99 records from BIRDRACE TEAM BO-BACHTER. 144 records from BIRDRACE Die Mohrenlerchen. 272 records from BIRDRACE Niederlausitz-Team. 274 records from BIRDRACE Asiola-Quartett. 139 records from BIRDRACE Turbine Untersee. 140 records from BIRDRACE Guckers Offenbach. 157 records from BIRDRACE Rheinische Wasserrallen. 118 records from BIRDRACE Die Lippegeier. 78 records from BIRDRACE leucorhö statt logorrhö. 82 records from BIRDRACE Die Ziegeneier. 84 records from BIRDRACE Bielefinken. 96 records from BIRDRACE OAG Neuwerk. 98 records from BIRDRACE Die Paradiesvögel. 100 records from BIRDRACE Stuttgart 100 trööt. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Akassine*. 287 records from BIRDRACE Pody und Co. 280 records from BIRDRACE Alb-Donaumoos-Kompetänzteam. 138 records from BIRDRACE Arkonauten. 1 records from Murcia ephippiata. 65 records from BIRDRACE Federal Birds of Investigation FBI. 69 records from BIRDRACE Pfeifenten. 166 records from BIRDRACE Die Düsselmöwen. 91 records from BIRDRACE NABU LV Hessen. 91 records from BIRDRACE SchrägeVögel. 79186 records from All Ireland Non-Marine Molluscan Database. 106 records from BIRDRACE EFTAS-NLU Birdrace Team 2008. 149 records from BIRDRACE Birding Bentheim. 114 records from BIRDRACE VIE will rock you!. 101 records from BIRDRACE Enger am Spektiv. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Bkassine*. 132 records from BIRDRACE Die Wetterauer. 123 records from BIRDRACE Unterste Niederrhein-Rennvögel. 114 records from BIRDRACE Di-Bi-Di-Birder. 109 records from BIRDRACE Die Borner. 2910 records from A checklist to the wasps of Peru (Hymenoptera, Aculeata). 66 records from Langes Tannen(LMS), Klasse 5d. 54 records from VFD-H: MIttelgebirgsweide. 62 records from Lebensraum Dorf. 50 records from BIRDRACE Schwarzstorchbruthöhlen-Initiative Rügen. 84 records from BIRDRACE Birding for Nature. 126 records from BIRDRACE Die Schwenker-Birder. 396 records from Colección de Entomología - Auchenorrhyncha. 110 records from BIRDRACE Linumer Luchschleicher. 27 records from Schulgarten Waldorfschule Hassfurt. 102 records from BIRDRACE Willi goes Birding. 102 records from BIRDRACE Buteo1DO. 103 records from BIRDRACE federleser. 106 records from BIRDRACE Die Göttinger Sozialbrachvögel. 104 records from BIRDRACE Erlanger Piepmätzchen. 104 records from BIRDRACE Die Marburger-Vogelwelt.de radelt. 105 records from BIRDRACE Kiesmätze. 105 records from BIRDRACE coesfelder_vogelkundler. 106 records from BIRDRACE Ave Goettingen!. 1 records from Beitrage zur Kenntniss paläarctischer Myriopoden. XV. Aufsatz: Lithobiiden aus Bosnien, Herzogovina und Dalmatien. 134 records from BIRDRACE Griffin Wood Warblers. 131 records from BIRDRACE Brut. 126 records from BIRDRACE Duckehühnchen. 123 records from BIRDRACE INTERNETLITHO feat Fliegende Füchse. 120 records from BIRDRACE The early birds. 119 records from BIRDRACE Tick, Trick und Track. 112 records from BIRDRACE Gütersloher Gimpel. 110 records from BIRDRACE Angeliter Ornis. 402 records from Tag der Artenvielfalt in Heidelberg. 504 records from Schatzinsel Wangerooge. 116 records from Sürther Aue. 264 records from Artenvielfalt im Naturschutzgebiet an der Loreley - Leiselfeld/Spitznack - 2. Jahr. 102 records from http://www.geo-artenvielfalt.de (www.geo-artenvielfalt.de) - BIRDRACE *Ckassine*. 103 records from BIRDRACE Die Otzberger. 174 records from BIRDRACE Bon(n)apartemöwen. 129 records from BIRDRACE Oostfreesland Bird-Lopers. 112 records from BIRDRACE Hügelland zu Fuß. 67 records from Tongrube bei Hettstedt. 173 records from FFH-Gebiet Klosterwasser/Burkau. 37 records from Liether Park 2 (LMS), Klasse 6c. 121 records from Owere Fiddel. 248 records from Schulgarten der Volksschule. 2 records from Neue Oribatiden (Acari) aus Deutschland III. Suctobelba carcharodon n. sp. und Suctobelba prominens n. sp.. 101 records from Steinbruch Kronungen. 85 records from Rund um den Hainbergsee. 96 records from "Ahrschleife bei Altenahr". 36 records from Artenvielfalt in der Quälingsbachaue Gladbeck. 49 records from VFD-H.: Rheingau: Bärstadt. 58 records from VFD-H. Heidenrod: Mähweide im Wasserschutzgebiet. 36 records from Liether Park 1 (LMS), Klasse 5b. 269 records from BIRDRACE speedbirder. 269 records from BIRDRACE Dithmarscher Deichhühner. 88 records from BIRDRACE Kingfisher. 143 records from BIRDRACE Die Laufenten. 177 records from BIRDRACE Mehr Seh Team. 103 records from BIRDRACE Resopal-Darmstadt-Dieburg. 114 records from BIRDRACE LiLaLau. 111 records from BIRDRACE Die Wendehälse. 4500 records from (Figure 7) Distribution of Cretaceous planktonic foraminifers and associated organisms from DSDP Hole 77-540. 121 records from BIRDRACE Immerwiederhopf. 107 records from BIRDRACE Herford Birders. 107 records from BIRDRACE Borussia Zippammer. 277 records from Naturschutzgebiet Börstig bei Hallstadt. 44 records from Wiesen am Treffpunkt Freizeit. 145 records from Gronau - auf der Suche nach dem Neunauge. 144 records from Lustbach-Umland. 54 records from Königsdorfer Wald. 73 records from VFD-HH/SH: Pferdweide Lammert. 106 records from NSG Forst Zinna-Jüterbog-Keilberg. 62 records from Hettstadt Gehäge. 234 records from Wiesen-Wälder-Wasser um Dansenberg, Biosphärenreservat Pfälzerwald. 709 records from "Laubenheimer Bodenheimer Ried" - von Stromtalwiesen und Flutrasen. 113 records from Tornoer Teich. 144 records from VFD-RP: Hunsrück: Pferdeweide Kucher. 99 records from Streuobstwiese Stedar. 114 records from Liether Kalkgrube. 37 records from Naturbelassene ehemalige Wiese am Haselbach (Privates Schutzgebiet). 80 records from Feldweg Waldkirchen. 194 records from Bodenteicher Seewiesen. 61 records from Wälder im Hainbachtal. 108 records from BIRDRACE Diesmal sehen wir mehr. 54 records from Biotope im Schulumfeld. 120 records from VFD-H: Heidenrod: Beckers Weide mit Wald. 132 records from Aachtobel. 83 records from VFD-H: Heidenrod: Weide am Ortsrand. 54 records from Wir erkunden die Hofau, Klasse 5c. 102 records from BIRDRACE Niederrheinische Bartgeier. 104 records from BIRDRACE Andechser Stativträger. 120 records from BIRDRACE Ornis im Einsatz. 75 records from BIRDRACE Die Kartoffelsäcke. 48 records from Wahner Heide LK 12 Biologie. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland 2. 6325 records from Colección Entomológica de la Universidad de Antioquia. 82 records from Teich im Wald zwischen Böblingen und Schönaich. 13 records from Vergleich der Fauna eines naturbelassenen mit einem wasserwirtschaftlich veränderten Gewässer. 24 records from Klassenfahrt Usedom / Wald und Küste in Zinnowitz. 11 records from Umgebung Jugendherberge Clausthal, Klasse 8d. 17 records from Hydrolagus mccoskeri sp. nov., a new species of chimaeroid fish from the Galápagos Islands (Holocephali: Chimaeriformes: Chimaeridae).. 214 records from Pflanzen und Tiere im Burgwald. 29 records from Waldwiese. 66 records from Von der Nutzung zur Natur. 61 records from BIRDRACE Baumläufer. 76 records from BIRDRACE Nachtigallen. 79 records from BIRDRACE Blinde Hühner. 83 records from BIRDRACE Die Frankenpfeifer. 104 records from BIRDRACE Die Vriesischen Feigen-Vögel (VFV). 45 records from IBF Monitoring of Orthoptera. 176 records from BIRDRACE Professorenteam. 128 records from BIRDRACE Die TUErteltauben. 69 records from Unter hellen Zinnen und finsteren Grotten. 30 records from Geführte Wanderung im Eselsbachtal. 16324 records from Herbarium specimens of Société des Sciences Naturelles et Mathématiques de Cherbourg (CHE). 184 records from Chinese species of egg-parasitoids of the genera Oxyscelio Kieffer, Heptascelio Kieffer and Platyscelio Kieffer (Hymenoptera: Platygastridae s.l., Scelioninae). 52 records from Aktion der Klasse H2 in Simmelsberg. 66 records from BIRDRACE Die schrägen Vögel aus dem Sauerland. 89 records from BIRDRACE Uttenreuther Spatzenzähler. 90 records from BIRDRACE TicTacToe. 101 records from BIRDRACE nabu-rhein-main.de. 18 records from Landschaftsschutzgebiet Buchhorst2. 94 records from FFH-Gebiet Paartal. 84 records from BIRDRACE Vogelscheuchen. 88 records from BIRDRACE Vogelkucker. 31 records from Düpenauwiesen. 35 records from Scottish Natural Heritage - Information on capercaillie distribution collected during the âProductivity of breeding Capercaillie Tetrao urogallus at sites across their Scottish range 2011â monitoring project.. 152 records from BIRDRACE NAJU-Aspach. 99 records from VFD HH/SH "Pferdeweide Lemsahl". 33 records from Schüler erforschen die Helme-Aue. 40 records from BUND Naturschutzzentrum St. Julian. 5374 records from NX - Herbário Nova Xavantina. 30 records from Leben auf einer Sturmfläche. 334 records from (Appendix 2) Stratigraphic distribution of key and potential stratigraphic calcareous nannofossil markers in the upper Campanian-Maastrichtian of ODP Hole 122-762C. 47 records from Schulgelände Grolland. 69 records from BIRDRACE Mathilden-Käuze. 21 records from Sonntagmorgen-Veranstaltungen im Zeichen des GEO-Tags. 146 records from BIRDRACE VdW Wilder Westen. 38 records from Was lebt in der Brutzwiese?. 1087 records from The Bat Conservation Trust - Bechstein's Bat Survey Project. 54 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >125 µm. 126 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, >125 µm fraction. 35 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, >125 µm fraction. 370 records from Benthic foraminifera counts of sediment core PS1244-2 (GIK23244-2). 3 records from Rivulus sape, a new species of killifish (Cyprinodontiformes: Rivulidae) from the Paragua River system, Caroní River drainage, Guyana Shield, Venezuela.. 57 records from Schulgarten Janusz-Korczak-Realschule. 17 records from Bachrenaturierung Littfe. 17 records from Feuchtwiese am Nationalpark-Haus Neuwerk. 30 records from Höhle am Neuweg / Sächsische Schweiz. 1 records from Streuobstwiese Alt Necheln. 259 records from Benthic foraminifera accumulation rate and benthic foraminiferal productivity proxies at ODP Site 165-999 in the Caribbean (Appendix A). 88 records from Abundance of benthic foraminifera in late Paleocene to eraly Pliocene sediments of DSDP Hole 74-525A on the Walvis Ridge, South Atlantic (Table 1). 31 records from Benthic foraminifera counts of sediment core PS2644-2. 53 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 63-125 µm. 4960 records from NRM-Herpetology. 38 records from Aktionstag "Artenvielfalt der Feuchtwiesen bei Daubringen". 53 records from BIRDRACE Taubenhaucher. 63 records from Rosarium (LMS), Klasse 6a. 45 records from Reusaer Wald. 58 records from Schulgarten Zinnowwald-GS. 42 records from Feuchtwiese Grüne Mitte, Klasse 5a. 30 records from Riekdahler Wiesen. 18 records from GEO-Tag der Artenvielfalt der Klasse 7c am Gymnasium Allee im Wohlers Park. 77 records from VFD-RP: Taunus: Mähweide Dehe. 2179 records from (Table 7) Absolute abundances of benthic foraminifera in Neogene sediments of DSDP Site 90-588_Site in the southwest Pacific. 61 records from (Table 1) Sedimentology of core D11957P. 9126 records from (Appendix 3) Assemblage of benthic foraminifera in sediment core M5/2_KL15. 117 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >125 µm. 22 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 30-63 µm. 192 records from Total living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >30 µm. 64 records from Rechts des Inn Höhe Hofau Rosenheim. 18 records from Schulgarten der Gesamtschule Am Heidberg. 12 records from Art´n Vielfalt im Kinderwald. 7 records from Die Bachspezies. 17 records from Nachtinsekten am Muldenufer. 51 records from Kindervilla Außengelände. 12 records from Flora und Fauna am Mühlberg. 192 records from "Schwarzwassertal" bei Pobershau. 64 records from (Appendix A) Stable isotope ratios of Cibicidoides sp. and planktonic foraminifera from the Mid-Miocene of ODP Hole 119-744B of the Kerguelen Plateau, Antarctica. 52 records from Sedimentology and stratigraphy of core OD96_41:4:1. 66 records from (Table 2) Abundance of benthic foraminifers of sediment core PS2137-1. 930 records from Benthic foraminifera counts of sediment core PS2644-5. 59 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >125 µm. 159 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction >125 µm. 64 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >125 µm. 530 records from Benthic foraminifera counts of sediment core GIK23352-3. 5477 records from Colección de mamíferos de la Universidad del Valle. 43 records from Living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction 63-125 µm. 35 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 63-125 µm. 26 records from Living benthic foraminifera at station M33/1_MC-25 (EAST), size fraczion 63-125 µm. 158 records from Total living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction >30 µm. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, >125 µm fraction. 37 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, >125 µm fraction. 14 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 63-125 µm fraction. 76 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, 63-125 µm fraction. 152 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-35. 25 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >125 µm. 46 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 63-125 µm. 43 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 63-125 µm. 17 records from Living benthic foraminifera at station M33/1_MC-13 (WAST-T), size fraction 30-63 µm. 26 records from Living benthic foraminifera at station M33/1_MC-15 (WAST), size fraction 30-63 µm. 39 records from Living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction 30-63 µm. 8 records from Living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction 30-63 µm. 123 records from Total living benthic foraminifera at station M33/1_MC-19 (CAST), size fraction >30 µm. 2 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 30-63 µm fraction. 108 records from Total living benthic foraminifera at station M33/1_MC-03 (NAST), size fraction >30 µm. 66 records from Total living benthic foraminifera at station M33/1_MC-30 (SAST), size fraction >30 µm. 18 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, >125 µm fraction. 87 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-35, >125 µm fraction. 16 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-18, 63-125 µm fraction. 10 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-02, 30-63 µm fraction. 56 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-02. 214 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-43. 96 records from Assemblage of total living benthic foraminifera in sediment core SO118_MC-51. 16 records from Assemblage of living benthic foraminifera in sediment core SO129_MC-09, 63-125 µm fraction. 65 records from Total living benthic foraminifera at station M33/1_MC-25 (EAST), size fraction >30 µm. 250 records from Record, the Biodiversity Information System for Cheshire, Halton, Warrington and the Wirral - RECORD Cetacean data up to current day. 56 records from (Appendix A) Pollen and spore counts at DSDP Hole 64-480. 143 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-43, 63-125 µm fraction. 27 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-04, 30-63 µm fraction. 56 records from Assemblage of living benthic foraminifera in sediment core SO118_MC-52, 30-63 µm fraction. 114 records from Assemblage of total living benthic foraminifera in sediment core SO
Keywords: GBIF; biodiversity; species occurrences